Photon counting in stellar intensity interferometry: current status and future prospects - Horch, Elliott P. (Advanced Photon Counting Techniques XIX, 2025)
Intensity interferometry, also known as the Hanbury Brown and Twiss effect, has seen significant interest in astronomy in recent years. The method involves recording timing correlations between photons received at two or more telescopes in order to derive extremely high spatial resolution information about an astronomical object, potentially including imaging stellar surfaces and other objects at unprecedented scales. This paper will briefly review the technique, discuss the performance characteristics of the of photon counters used in modern intensity interferometers, and describe opportunities for the future. As an example of photon counting with a working instrument, observing experiences with the Southern Connecticut Stellar Interferometer (SCSI), a three-station instrument using single-photon avalanche diode (SPAD) detectors, will be described. The recent lessons learned with this and other instruments in use today give a clear picture of the next steps needed to upgrade efficiency and successfully observe fainter objects. If successful, these improvements would provide a strong argument for creating situations where intensity interferometers can have baselines of one to several kilometers, which would unlock the spatial detail needed to address several exciting astrophysical questions.
Keywords: Astronomy; Current (fluid); Intensity (physics); Interferometry; Optics; Photon; Photon counting; Physics; dept.phy

Cutting the cord: toward wireless optical intensity interferometry - Horch, Elliott P (Proceedings of SPIE, 2015)
Intensity interferometry, which was first used for obtaining ultra-high-resolution image information in astronomy in the 1960's and 1970's, is now being revived using modern detectors and electronics. This paper explores the possibility of wireless optical interferometry made possible by technological advancements in timing correlation, signal processing, and detector technology. If this can be achieved, then baselines of one to several kilometers may be possible in optical interferometry in the coming years. This would improve the resolution over the current generation of amplitude-based optical interferometers by a factor of at least ten. © COPYRIGHT SPIE. Downloading of the abstract is permitted for personal use only. © 2015 SPIE.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/068-868-231-716-094 tex.type: [object Object]
Keywords: Avalanche diodes; Correlation detectors; Current generation; Detector technology; Interferometry; Optical correlation; Optical interferometer; Optical interferometry; Particle beams; Photon counting; Photons; Signal processing; Single photon avalanche diode; Single photon avalanche diodes; Technological advancement; Timing correlation; Ultra-high-resolution astronomy; Ultrahigh resolution; dept.phy

Speckle imaging at large telescopes: current results and future prospects - Horch, Elliott P (Proceedings of SPIE, 2016)
In recent years, speckle imaging has proven very useful for certain problems in single-Aperture high-resolution imaging, including searching for faint stellar companions near exoplanet host stars and for satellite imaging. These developments have largely been the result of the availability of electron-multiplying CCD cameras, which allow for greater sensitivity and better photometric linearity when compared with other detectors that have comparable speed. This in turn has led to an increased use for speckle imaging at mid-sized and large telescopes. Some results of these efforts will be discussed, and the outlook for the future of speckle will be given. © 2016 SPIE.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/043-284-682-979-188 tex.type: [object Object]
Keywords: CCD cameras; Electron multiplying ccds; Faint Companion Detection; Future prospects; High resolution; High-Resolution Astronomy; High-resolution imaging; Image Reconstruction; Image reconstruction; Interferometry; Large telescopes; Satellite imaging; Single aperture; Speckle; Speckle Imaging; Speckle imaging; Telescopes; dept.phy

Speckle interferometry of secondary components in nearby visual binaries - Tokovinin, Andrei; Horch, Elliott P (The Astronomical Journal, 2016)
Statistical characterization of secondary subsystems in binaries helps to distinguish between various scenarios of multiple-star formation. The Differential Speckle Survey Instrument was used at the Gemini-N telescope for several hours in 2015 July to probe the binarity of 25 secondary components in nearby solar-type binaries. Six new subsystems were resolved, with meaningful detection limits for the remaining targets. The large incidence of secondary subsystems agrees with other similar studies. The newly resolved subsystem HIP 115417 Ba,Bb causes deviations in the observed motion of the outer binary from which an astrometric orbit of Ba,Bb with a period of 117 years is deduced. © 2016. The American Astronomical Society. All rights reserved.
17 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/112-209-617-018-947 tex.type: [object Object]
Keywords: binaries: visual; dept.phy; peer-reviewed; stars: low-mass

High-resolution speckle imaging - Howell, Steve B.; Horch, Elliott P. (Physics Today, 2018)
3 citations (Crossref) [2023-10-31]
Keywords: dept.phy

Wide-field speckle techniques for small, urban telescopes - Granucci, Nicole M.; Horch, Elliott P. (Optical and Infrared Interferometry and Imaging VI, 2018)
Recent work with the NESSI speckle camera at Kitt Peak and the 'Alopeke speckle camera at Gemini-North indicates that speckle data reduction techniques can be successfully modified to produce high-resolution images over fields that are at least tens of arc seconds across. While these wide-field speckle image reconstructions are not diffraction-limited, the improvement in resolution over the seeing-limited case can be substantial. In this paper, we explore the application of these techniques to data taken with a small (0.6-m) telescope in an urban environment. Many telescopes located in urban communities, such as New Haven, Connecticut, where Southern Connecticut State University resides, have limited use scientifically due to substantial light pollution, poor seeing, poor telescope tracking, and other issues. We will present initial data using our set-up and discuss the potential for this approach for improving the imaging capabilities of small telescopes on our campus and beyond.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/033-406-183-484-56X, pop00246
Keywords: Cameras; Diffraction limited; High resolution image; Image enhancement; Image reconstruction; Imaging capabilities; Interferometry; Pollution; Reduction techniques; Shift-and-add; Speckle; Speckle imaging; Telescopes; Unsharp masking; Urban environments; dept.phy; shift-and-add techniques; unsharp masking

Portable intensity interferometry - Horch, Elliott P; Camarata, Matthew A (Proceedings of SPIE, 2012)
A limitation of the current generation of long baseline optical interferometers is the need to make the light interfere prior to detection. This is unlike the radio regime where signals can be recorded fast enough to use electronics to accomplish the same result. This paper describes a modern optical intensity interferometer based on electronics with picosecond timing resolution. The instrument will allow for portable optical interferometry with much larger baselines than currently possible by using existing large telescopes. With modern electronics, the limiting magnitude of the technique at a 4-m aperture size becomes competitive with some amplitude-based interferometers. The instrumentation will permit a wireless mode of operation with GPS clocking technology, extending the work to extremely large baselines. We discuss the basic observing strategy, a planned observational program at the Lowell Observatory 1.8-m and 1.0-m telescopes, and the science that can realistically be done with this instrumentation. © 2012 SPIE.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/097-846-651-777-744 tex.type: [object Object]
Keywords: Aperture sizes; Binary star; Binary stars; Current generation; Intensity interferometry; Interferometers; Interferometry; Large telescopes; Long base line; Mode of operations; Optical intensities; Optical interferometer; Optical interferometry; Optical telescopes; Picosecond timing; Single photon avalanche diode; Single photon avalanche diodes; Stars; Stellar disks; Stellar radii; Telescopes; dept.phy

A New Stellar Companion to GJ 835 - Clark, Catherine A.; Horch, Elliott; Davidson, James W. (Research notes of the AAS, 2023)
Num Pages: 1
Keywords: dept.phy

Stellar photon correlation detection with the Southern Connecticut stellar interferometer - Weiss, Samuel A.; Rupert, Justin D.; Horch, Elliott P. (Optical and Infrared Interferometry and Imaging VI, 2018)
The Southern Connecticut Stellar Interferometer (SCSI) is a portable optical intensity interferometer located on the campus of Southern Connecticut State University in New Haven, Connecticut. Since its completion in 2016, the instrument has been used to take engineering data of bright stars. This paper will discuss the data collection and analysis methods, as well as the progress toward reliably measuring a significant stellar photon correlation. Vega has been the main star chosen for test observations to date because its diameter is well known by other methods, and it is not an extended source for the baselines used. The correlation peak in the processed data is compared to theoretical expectations. Given our expected sensitivity, a significant correlation peak is expected for small baselines (~2 m) to appear after a few hours of observation. So far, the observations indicate that the correlation peak is at the expected time delay, and the signal-to-noise ratio roughly scales as predicted.
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/067-933-668-471-503, pop00212
Keywords: Avalanche diodes; Correlation peaks; Engineering data; Extended sources; Hanbury Brown and Twiss effect; Intensity interferometry; Interferometers; Interferometry; Optical intensities; Particle beams; Photon correlation; Photons; Quantum optics; Signal to noise ratio; Single photon avalanche diode; Stars; Stellar interferometers; dept.phy; single-photon avalanche diode (SPAD) detectors; timing correlation

Differential speckle and wide-field imaging for the Gemini-North and WIYN telescopes - Scott, Nicholas J; Howell, Steve B; Horch, Elliott P (Proceedings of SPIE, 2016)
Two new instruments are currently being built for the Gemini-North and WIYN telescopes. They are based on the existing DSSI (Differential Speckle Survey Instrument), but the new dual-channel instruments will have both speckle and "wide-field" imaging capabilities. Nearly identical copies of the instrument will be installed as a public access permanent loan at the Gemini-N and WIYN telescopes. Many exoplanet targets will come from the NASA K2 and TESS missions. The faint limiting magnitude, for speckle observations, will remain around 16 to 17th magnitude depending on observing conditions, while wide-field, high speed imaging should be able to go to 21+. For Gemini, the instrument will be remotely operable from either the mid-level facility at Hale Pohaku or the remote operations base in Hilo. © 2016 SPIE.
8 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/030-410-801-313-630 tex.type: [object Object]
Keywords: High resolution imaging; High speed imaging; High-resolution imaging; Image reconstruction; Imaging capabilities; Instrumentation; Interferometry; NASA; Remote operation; Speckle; Speckle interferometry; Survey instruments; Telescopes; Wide field imaging; dept.phy

On the occurrence rate of hot jupiters in different stellar environments - Wang, Ji; Fischer, Debra A; Horch, Elliott P; Huang, Xu (The Astrophysical Journal, 2015)
Many hot Jupiters (HJs) are detected by the Doppler and transit techniques. From surveys using these two techniques, however, the measured HJ occurrence rates differ by a factor of two or more. Using the California Planet Survey sample and the Kepler sample, we investigate the causes for this difference in the HJ occurrence rate. First, we find that 12.8% ± 0.24% of HJs are misidentified in the Kepler mission because of photometric dilution and subgiant contamination. Second, we explore the differences between the Doppler sample and the Kepler sample that can account for the different HJ occurrence rate. Third, we discuss how to measure the fundamental HJ occurrence rates by synthesizing the results from the Doppler and Kepler surveys. The fundamental HJ occurrence rates are measures of the HJ occurrence rate as a function of stellar multiplicity and evolutionary stage, e.g., the HJ occurrence rate for single and multiple stars or for main-sequence and subgiant stars. While we find qualitative evidence that HJs occur less frequently in subgiants and multiple stellar systems, we conclude that our current knowledge of stellar properties and the stellar multiplicity rate is too limited for us to reach any quantitative result for the fundamental HJ occurrence rates. This concern extends to ηEarth, the occurrence rate of Earth-like planets. © 2015. The American Astronomical Society. All rights reserved.
54 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/156-890-481-368-476 tex.type: [object Object]
Keywords: Fundamental parameters stars; Methods; Photometric techniques; Radial velocities; Solar-type stars; Statistical planets and satellites; Statistics techniques; dept.phy

A search for binary star companions to the KELT planet hosts and a comparison sample. i. results of DSSI observations - Coker, Carl T.; Gaudi, B. Scott; Pogge, Richard W.; Horch, Elliott (The Astronomical Journal, 2017)
We are conducting a search for binary companions around 11 hot-Jupiter hosts from the Kilodegree Extremely Little Telescope (KELT) survey and a large comparison sample of stars shown by KELT to not host a transiting hot Jupiter. The primary stars are bright (7.5 < V < 11) and of similar distance from Earth (100 < d < 300 pc). In this paper, we present the results of our observations using the Differential Speckle Survey Instrument. We observed 9 of the 14 KELT planet hosts that are visible from the northern hemisphere and 51 comparison stars, discovering two new potential companions and re-observing two previously known possible binary systems and one confirmed binary system. We provide an estimate of the chance alignment probability for our observed candidate binaries. © 2017 The American Astronomical Society. All rights reserved.
3 citations (Crossref) [2023-10-31]
Keywords: Astrometry; binaries: close; binaries: general; dept.phy; peer-reviewed; planets and satellites: detection; planets and satellites: formation

The Three-dimensional orbit, orbital parallax, and individual masses of the double-lined spectroscopic binaries HD 183255, HD 114882, and HD 30712 - Docobo, J. A.; Campo, P. P; Gomez, J.; Horch, Elliott P. (The Astronomical Journal, 2018)
Recent speckle observations performed at the Discovery Channel Telescope, the Gemini North Telescope, and the Special Astrophysical Observatory 6 m Telescope have permitted us to calculate the visual orbit of SB2 HD 114882 for the first time and to improve the visual orbits of two other SB2 systems, HD 30712 and HD 183255, using algorithms published by the authors of this research. Recently, new high-quality spectroscopic orbits have been obtained for these binaries by other authors. We determine their 3D orbits, individual masses, and orbital parallaxes, and present them in this paper. The parallaxes are compared with those available from the Gaia mission, and a comparison between the values confirms the precision of the results obtained here. © 2018. The American Astronomical Society. All rights reserved.
4 citations (Crossref) [2023-10-31]
Keywords: astrometry; binaries: spectroscopic; binaries: visual; dept.phy; peer-reviewed; stars: fundamental parameters; techniques: interferometric

An analytic algorithm to calculate the inclination, ascending node, and semimajor axis of spectroscopic binary orbits using a single speckle measurement and the parallax - Docobo, Jose Angel; Campo, P P; Andrade, Manuel; Horch, Elliott P (Astrophysical Bulletin, 2014)
It is well known that in spectroscopic binary orbits, the inclination, the ascending node, and the semimajor axis remain undetermined, therefore the principal objective of this research is to establish an analytic methodology for the calculation of these parameters for spectroscopic binaries, both single-lined (SB1) and double-lined (SB2). In other words, the goal is to determine their “three-dimensional” orbits using a single speckle measurement (ρ, θ, t) and the parallax (π). Moreover, estimates of the individual masses of each system can also be obtained. The proposed algorithm was successfully applied to SB1 systems: YSC 148 (HD 37393) and CHR 225 (HD 34318), and SB2 systems: LSC 1 Aa1,2 (HD 200077) and Mkt 11 Aa, Ab (HD 358). In this late case, previously determined spectroscopic and visual orbits have been used to compare and contrast the results obtained from them with our results. The methodology presented is especially interesting for those cases in which it is only possible to resolve the spectroscopic binary in the zones of maximum angular separation by optical means thereby making it impossible to avail of sufficient observations in order to calculate the visual orbit. © Pleiades Publishing, Ltd. 2014.
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/094-814-675-311-054 tex.type: [object Object]
Keywords: dept.phy; general; high angular resolution—techniques; interferometric—binaries; techniques

Influence of stellar multiplicity on planet formation. III. adaptive optics imaging of kepler stars with gas giant planets - Wang, Ji; Fischer, Debra A.; Horch, Elliott P.; Xie, Ji-Wei (The Astrophysical Journal, 2015)
As hundreds of gas giant planets have been discovered, we study how these planets form and evolve in different stellar environments, specifically in multiple stellar systems. In such systems, stellar companions may have a profound influence on gas giant planet formation and evolution via several dynamical effects such as truncation and perturbation. We select 84 Kepler Objects of Interest (KOIs) with gas giant planet candidates. We obtain high-angular resolution images using telescopes with adaptive optics (AO) systems. Together with the AO data, we use archival radial velocity data and dynamical analysis to constrain the presence of stellar companions. We detect 59 stellar companions around 40 KOIs for which we develop methods of testing their physical association. These methods are based on color information and galactic stellar population statistics. We find evidence of suppressive planet formation within 20 AU by comparing stellar multiplicity. The stellar multiplicity rate (MR) for planet host stars is 0+5-0% within 20 AU. In comparison, the stellar MR is 18% ± 2% for the control sample, i.e., field stars in the solar neighborhood. The stellar MR for planet host stars is 34% ± 8% for separations between 20 and 200 AU, which is higher than the control sample at 12% ± 2%. Beyond 200 AU, stellar MRs are comparable between planet host stars and the control sample. We discuss the implications of the results on gas giant planet formation and evolution. © 2015. The American Astronomical Society. All rights reserved.
59 citations (Crossref) [2023-10-31] Citation Key Alias: pop00037 tex.type: [object Object]
Keywords: dept.phy; methods: observational; methods: statistical; planet-star interactions; planetary systems; planets and satellites: formation; techniques: high angular resolution

Stellar companions of exoplanet host stars in K2 - Matson, Rachel A.; Howell, Steve B.; Horch, Elliott P.; Everett, Mark E. (The Astronomical Journal, 2018)
It is well established that roughly half of all nearby solar-type stars have at least one companion. Stellar companions can have significant implications for the detection and characterization of exoplanets, including triggering false positives and masking the true radii of planets. Determining the fraction of exoplanet host stars that are also binaries allows us to better determine planetary characteristics as well as establish the relationship between binarity and planet formation. Using high angular resolution speckle imaging, we detect stellar companions within ∼1 arcsec of K2 planet-candidate host stars. Comparing our detected companion rate to TRILEGAL star count simulations and known detection limits of speckle imaging, we estimate the binary fraction of K2 planet host stars to be 40%-50%, similar to that of Kepler exoplanet hosts and field stars. © 2018. The American Astronomical Society. All rights reserved.
70 citations (Crossref) [2023-10-31]
Keywords: binaries: general; binaries: visual; dept.phy; peer-reviewed; planetary systems; techniques: high angular resolution

The NN-explore exoplanet stellar speckle imager: Instrument description and preliminary results - Scott, Nicholas J.; Howell, Steve B.; Horch, Elliott P.; Everett, Mark E. (Publications of the Astronomical Society of the Pacific, 2018)
A new speckle and wide-field imaging instrument for the WIYN telescope called NN-EXPLORE Exoplanet Stellar Speckle Imager (NESSI) is described. NESSI offers simultaneous two-color diffraction-limited imaging and wide-field traditional imaging for validation and characterization of transit and precision RV exoplanet studies. Many exoplanet targets will come from the NASA K2 and Transiting Exoplanet Survey Satellite (TESS) missions. NESSI is capable of resolving close binaries at sub-arcsecond separations down to the diffraction limit and >6 mag contrast difference in the visible band on targets as faint as 14th mag. Preliminary results from the instrument commissioning at WIYN and demonstrations of the instrument’s capabilities are presented. © 2018. The Astronomical Society of the Pacific. Printed in the U.S.A.
68 citations (Crossref) [2023-10-31]
Keywords: Binaries (including multiple): close; Instrumentation: high angular resolution; Instrumentation: interferometers; Techniques: interferometric; Techniques: photometric; dept.phy; peer-reviewed

Understanding the effects of stellar multiplicity on the derived planet radii from transit surveys: implications for kepler, k2, and TESS - Ciardi, David R; Beichman, Charles A; Horch, Elliott P; Howell, Steve B (The Astrophysical Journal, 2015)
We present a study on the effect of undetected stellar companions on the derived planetary radii for Kepler Objects of Interest (KOIs). The current production of the KOI list assumes that each KOI is a single star. Not accounting for stellar multiplicity statistically biases the planets toward smaller radii. The bias toward smaller radii depends on the properties of the companion stars and whether the planets orbit the primary or the companion stars. Defining a planetary radius correction factor, XR, we find that if the KOIs are assumed to be single, then, on average, the planetary radii may be underestimated by a factor of 〈XR〉 ≈ 1.5. If typical radial velocity and high-resolution imaging observations are performed and no companions are detected, then this factor reduces to 〈XR〉 ≈ 1.2. The correction factor 〈XR〉 is dependent on the primary star properties and ranges from 〈XR〉 ≈ 1.6 for A and F stars to 〈XR〉 ≈ 1.2 for K and M stars. For missions like K2 and TESS where the stars may be closer than the stars in the Kepler target sample, observational vetting (primary imaging) reduces the radius correction factor to 〈XR〉 ≈ 1.1. Finally, we show that if the stellar multiplicity rates are not accounted for correctly, then occurrence rate calculations for Earth-sized planets may overestimate the frequency of small planets by as much as 15%-20%. © 2015. The American Astronomical Society. All rights reserved.
182 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/088-016-640-995-341 tex.type: [object Object]
Keywords: binaries: general; dept.phy; planetary systems

Observations of binary stars with the differential speckle survey instrument. iv. observations of kepler, corot, and hipparcos stars from the gemini north telescope - Horch, Elliott P.; Howell, Steve B.; Everett, Mark E.; Ciardi, David R. (The Astronomical Journal, 2012)
We present the results of 71 speckle observations of binary and unresolved stars, most of which were observed with the DSSI speckle camera at the Gemini North Telescope in 2012 July. The main purpose of the run was to obtain diffraction-limited images of high-priority targets for the Kepler and CoRoT missions, but in addition, we observed a number of close binary stars where the resolution limit of Gemini was used to better determine orbital parameters and/or confirm results obtained at or below the diffraction limit of smaller telescopes. Five new binaries and one triple system were discovered, and first orbits are calculated for other two systems. Several systems are discussed in detail. © 2012. The American Astronomical Society. All rights reserved..
79 citations (Crossref) [2023-10-31] Citation Key Alias: pop00016 tex.type: [object Object]
Keywords: astrometry; binaries: visual; dept.phy; peer-reviewed; techniques: high angular resolution; techniques: interferometric; techniques: photometric

Intensity interferometry for the 21st century - Horch, Elliott P.; van Belle, G. T.; Genet, R. M.; Holenstein, B. D. (Journal of Astronomical Instrumentation, 2013)
Advances in detector technology and electronic timing capabilities in recent years have resulted in a new opportunity for ultra-high resolution in astronomy using intensity interferometry. We have been working with this technology and describe here the potential as we see it. Two separate opportunities exist at present: The use of Single Photon Avalanche Diode (SPAD) detectors with existing research-grade telescopes and photomultipliers coupled with light bucket telescopes. In the future, there may also be potential for space-based intensity interferometry. While intensity interferometry is not likely to replace amplitude-based interferometry, it does have certain advantages in terms of portability, use of large baselines, narrow-band imaging, and imaging in the blue. We see a new possibility for its use particularly in stellar astrophysics for these reasons. © 2013 World Scientific Publishing Company.
9 citations (Crossref) [2023-10-31] Citation Key Alias: pop00124
Keywords: Instrumentation: Interferometers; dept.phy; high angular resolution; techniques: Interferometric

Speckle observations and orbits of multiple stars. - Tokovinin, Andrei; Everett, Mark E; Horch, Elliott P; Torres, Guillermo; Latham, David W (Astronomical Journal, 2019)
We report results of speckle-interferometric monitoring of visual hierarchical systems using the newly commissioned instrument NN-EXPLORE Exoplanet and Stellar Speckle Imager at the 3.5 m WIYN telescope. During one year, 390 measurements of 129 resolved subsystems were made, while some targets were unresolved. Using our astrometry and archival data, we computed 36 orbits (27 for the first time). Spectro-interferometric orbits of seven pairs are determined by combining positional measurements with radial velocities measured, mostly, with the Center for Astrophysics digital speedometers. For the hierarchical systems HIP 65026 (periods 49 and 1.23 yr) and HIP 85209 (periods 34 and 1.23 yr) we determined both the inner and the outer orbits using astrometry and radial velocities and measured the mutual orbit inclinations of 11.°3 ± 1.°0 and 12.°0 ± 3.°0, respectively. Four bright stars are resolved for the first time; two of those are triple systems. Several visual subsystems announced in the literature are shown to be spurious. We note that subsystems in compact hierarchies with outer separations less than 100 au tend to have less eccentric orbits compared to wider hierarchies. © 2019. The American Astronomical Society. All rights reserved..
13 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/097-296-370-783-044 tex.type: [object Object]
Keywords: dept.phy; peer-reviewed; ⛔ No DOI found

Speckle Interferometry at SOAR in 2018 - Tokovinin, Andrei; Mason, Brian D.; Mendez, Rene A.; Horch, Elliott P.; Briceño, Cesar (The Astronomical Journal, 2019)
The results of speckle interferometric observations at the 4.1 m Southern Astrophysical Research Telescope (SOAR) in 2018 are given, totaling 3097 measurements of 2427 resolved pairs with separations from 11 mas to 5.″9 (median 0.″15, magnitude difference up to 7 mag) and nonresolutions of 624 targets. This work continues our long-term speckle program. Its main goal is to monitor orbital motion of close binaries, including members of high-order hierarchies and Hipparcos pairs in the solar neighborhood. Also, pre-main-sequence stars in the Orion OB1 association were surveyed, resolving 26 out of 118 targets. In addition, we report the discovery of 35 new companions among field visual multiples (some of which are likely optical) and first-time resolutions of another 31 pairs. By combining the measurements given here with the published ones, we computed 76 orbits for the first time and updated orbital elements of 34 visual binaries. Their periods range from 0.65 to 1100 yr, and their quality varies from first tentative solutions of grade 5 to accurate elements of grades 1 and 2. Finally, a list of 53 spurious pairs discovered by various techniques and unresolved at SOAR is given. © 2019. The American Astronomical Society. All rights reserved..
28 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/174-863-467-125-303, pop00135 tex.type: [object Object]
Keywords: dept.phy; material: machine-readable tables; peer-reviewed

Speckle interferometry at SOAR in 2019 - Tokovinin, Andrei; Mason, Brian D.; Mendez, Rene A.; Costa, Edgardo; Horch, Elliott P. (The Astronomical Journal, 2020)
The results of speckle-interferometric observations at the 4.1 m Southern Astrophysical Research Telescope in 2019 are given, totaling 2555 measurements of 1972 resolved pairs with separations from 15 mas (median 0.″21) and magnitude difference up to 6 mag, and non-resolutions of 684 targets. We resolved for the first time 90 new pairs or subsystems in known binaries. This work continues our long-term speckle program. Its main goal is to monitor orbital motion of close binaries, including members of high-order hierarchies and Hipparcos pairs in the solar neighborhood. We give a list of 127 orbits computed using our latest measurements. Their quality varies from excellent (25 orbits of grades 1 and 2) to provisional (47 orbits of grades 4 and 5). © 2020 The American Astronomical Society. All rights reserved.
20 citations (Crossref) [2023-10-31] tex.ids: tokovininSpeckleInterferometrySOAR2020, tokovininSpeckleInterferometrySoar2020 tex.adsnote: Provided by the SAO/NASA Astrophysics Data System tex.adsurl: https://ui.adsabs.harvard.edu/abs/2020AJ....160....7T arXiv: 2005.05305 [astro-ph.SR] tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85087554458 tex.eid: 7 type: Article
Keywords: 1081; 154; 1777; Astrophysics - Solar and Stellar Astrophysics; Binary stars; Multiple stars; Visual binary stars; dept.phy; peer-reviewed

A comparison of spectroscopic versus imaging techniques for detecting close companions to kepler objects of interest - Teske, Johanna K; Everett, Mark E; Hirsch, Lea A; Furlan, Elise; Horch, Elliott P; Horch, Elliott P; Howell, Steve B; Ciardi, David R; Gonzales, Erica J; Crepp, Justin R (The Astronomical Journal, 2015)
Kepler planet candidates require both spectroscopic and imaging follow-up observations to rule out false positives and detect blended stars. Traditionally, spectroscopy and high-resolution imaging have probed different host star companion parameter spaces, the former detecting tight binaries and the latter detecting wider bound companions as well as chance background stars. In this paper, we examine a sample of 11 Kepler host stars with companions detected by two techniques - near-infrared adaptive optics and/or optical speckle interferometry imaging, and a new spectroscopic deblending method. We compare the companion effective temperatures (Teff) and flux ratios (FB/FA, where A is the primary and B is the companion) derived from each technique and find no cases where both companion parameters agree within 1σ errors. In 3/11 cases the companion Teff values agree within 1σ errors, and in 2/11 cases the companion FB/FA values agree within 1σ errors. Examining each Kepler system individually considering multiple avenues (isochrone mapping, contrast curves, probability of being bound), we suggest two cases for which the techniques most likely agree in their companion detections (detect the same companion star). Overall, our results support the advantage that the spectroscopic deblending technique has for finding very close-in companions (θ ≲ 0.″02-0.″05) that are not easily detectable with imaging. However, we also specifically show how high-contrast AO and speckle imaging observations detect companions at larger separations (θ ≥ 0.″02-0.″05) that are missed by the spectroscopic technique, provide additional information for characterizing the companion and its potential contamination (e.g., position angle, separation, magnitude differences), and cover a wider range of primary star effective temperatures. The investigation presented here illustrates the utility of combining the two techniques to reveal higher-order multiples in known planet-hosting systems. © 2015. The American Astronomical Society. All rights reserved.
14 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/163-960-215-288-558 tex.type: [object Object]
Keywords: binaries: general; dept.phy; peer-reviewed; planetary systems; techniques: high angular resolution; techniques: interferometric; techniques: photometric; techniques: spectroscopic

Mass-luminosity anomalies: Plausible evidence of recent stellar interaction in the extraordinary blue straggler S1082 - Quitral-Pierart, Amanda; Leigh, Nathan; Mathieu, Robert; Latham, David; Sandquist, Eric; Horch, Elliott (Astronomy and Astrophysics, 2025)
Context. We present an observational and theoretical study of the complex stellar system S1082 in the open cluster M67. This system consists of at least four stars: a blue straggler in a 1.07-day eclipsing binary with a main sequence star (binary A) and another blue straggler in a 1185-day orbit with an unknown companion (binary B). Aims. We analyzed observational data to obtain the orbital and stellar parameters of the components of the eclipsing system. We then explored mass transfer and dynamical encounter scenarios that could explain the derived properties of all of the components of S1082. Methods. We combined high-precision photometry from K2 and TESS with archival light curves, new radial-velocity measurements, and speckle imaging to refine the orbital and physical parameters of the system. To explore the formation pathways, we conducted binary evolution simulations with MESA and dynamical scattering experiments with FEWBODY, followed by a tidal evolution modeling procedure. Results. Our revised radial-velocity solutions yield significantly changed dynamical masses for binary A, reducing the tension with the cluster turnoff mass compared to previous studies. Speckle imaging shows two resolved components separated by 390 AU in projection and, in combination with the two spectroscopic orbits, this is suggestive of a hierarchical quadruple configuration. Our results suggest that the two blue stragglers formed separately, with later dynamical encounters assembling the present configuration. This work underscores the importance of stellar dynamics in shaping the evolution of complex stellar systems within cluster environments such as M67.
Keywords: Binary number; Binary star; Blue straggler; Blue stragglers; Cluster (spacecraft); Open clusters and associations: individual: M67; Photometry (optics); Speckle imaging; Star cluster; Stars: individual: S1082; Stellar evolution; Stellar mass; dept.phy

Speckle interferometry at SOAR in 2016 and 2017 - Tokovinin, Andrei; Mason, Brian D.; Hartkopf, William I.; Mendez, Rene A.; Horch, Elliott P. (The Astronomical Journal, 2018)
The results of speckle interferometric observations at the 4.1 m Southern Astrophysical Research Telescope in 2016 and 2017 are given, totaling 2483 measurements of 1570 resolved pairs and 609 non-resolutions. We describe briefly recent changes in the instrument and observing method and quantify the accuracy of the pixel scale and position angle calibration. Comments are given on 44 pairs resolved here for the first time. The orbital motion of the newly resolved subsystem BU 83 Aa,Ab roughly agrees with its 36-year astrometric orbit proposed by J. Dommanget. Most Tycho binaries examined here turned out to be spurious. © 2018. The American Astronomical Society. All rights reserved..
30 citations (Crossref) [2023-10-31]
Keywords: binaries: visual; dept.phy; peer-reviewed

High-resolution imaging transit photometry of Kepler-13AB - Howell, Steve B.; Scott, Nicholas J.; Matson, Rachel A.; Horch, Elliott P.; Stephens, Andrew (The Astronomical Journal, 2019)
Using the high-resolution imaging instrument, 'Alopeke, at the Gemini-N telescope, we obtained simultaneous two-channel time-series observations of the binary exoplanet host star Kepler13-AB. Our optical observations were obtained during a transit event of the exoplanet Kepler-13b and light curves were produced using both speckle interferometric and aperture photometry techniques. Both techniques confirm that the transiting object orbits the star Kepler-13A while different transit depths are seen across the optical wavelength range, being ∼2 times deeper in the blue. These measurements, as well as mass determinations in the literature, are consistent with Kepler-13b being a highly irradiated gas giant with a bloated atmosphere. Our observations highlight the ability of high-resolution speckle imaging to not only assess binarity in exoplanet host stars but robustly determine which of the stars the transiting object actually orbits. © 2019. The American Astronomical Society. All rights reserved.
10 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/165-359-450-283-875, pop00155 tex.type: [object Object]
Keywords: binaries: close; dept.phy; galaxies: photometry; instrumentation: high angular resolution; peer-reviewed; planetary systems; techniques: image processing

Speckle interferometry at SOAR in 2015 - Tokovinin, Andrei; Mason, Brian D; Hartkopf, William I; Mendez, Rene A; Horch, Elliott P (The Astronomical Journal, 2016)
The results of speckle interferometric observations at the Southern Astrophysical Research Telescope in 2015 are provided, totaling 1303 measurements of 924 resolved binary and multiple stars, and non-resolutions of 260 targets. The separations range from 12 mas to 3.″37 (median 0.″17); the maximum measured magnitude difference is 6.7 mag. We resolved 27 pairs for the first time, including 10 as inner or outer subsystems in previously known binaries, e.g., the 50 mas pair in Cha. Newly resolved pairs are commented upon. We discuss three apparently non-hierarchical systems that have been discovered in this series, arguing that their unusual configurations are the result of projection. The resolved quadruple system HIP 71510 is also studied. © 2016. The American Astronomical Society. All rights reserved..
38 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/001-730-326-407-996 tex.type: [object Object]
Keywords: binaries: general; dept.phy; peer-reviewed

Speckle interferometry at soar in 2014 - Tokovinin, Andrei; Mason, Brian D; Hartkopf, William I; Mendez, Rene A; Horch, Elliott P (The Astronomical Journal, 2015)
The results of speckle interferometric observations at the Southern Astrophysical Research Telescope (SOAR) telescope in 2014 are given. A total of 1641 observations were taken, yielding 1636 measurements of 1218 resolved binary and multiple stars and 577 non-resolutions of 441 targets. We resolved for the first time 56 pairs, including some nearby astrometric or spectroscopic binaries and ten new subsystems in previously known visual binaries. The calibration of the data is checked by linear fits to the positions of 41 wide binaries observed at SOAR over several seasons. The typical calibration accuracy is 0.°1 in angle and 0.3% in pixel scale, while the measurement errors are on the order of 3 mas. The new data are used here to compute 194 binary star orbits, 148 of which are improvements on previous orbital solutions and 46 are first-time orbits. © 2015. The American Astronomical Society. All rights reserved..
81 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/016-545-424-948-585 tex.type: [object Object]
Keywords: binaries: general; dept.phy; peer-reviewed

The solar neighborhood LIV: 54 orbits of M dwarf multiples within 30 pc with speckle interferometry at SOAR - Vrijmoet, Eliot; Tokovinin, Andrei; Henry, Todd; Winters, Jennifer; Jao, Wei‐Chun; Horch, Elliott (The Astronomical Journal, 2026)
Abstract We present 1066 speckle measurements of M dwarf multiples observed over 2021–2024, all taken with HRCam on the Southern Astrophysical Research 4.1 m telescope. Among these, 900 observations resolve companions in 212 pairs, with separations spanning 17 mas to 3 . ″ 4 and brightness differences ranging from 0 to 4.9 mag in the I filter. We have characterized the orbits of 54 of these companions, spanning periods of 0.67–30 yr, by combining our data with literature astrometry, radial velocities, and, in four cases, Hipparcos–Gaia accelerations. Among the orbits presented here are 28 that are the first-ever such characterizations for their systems and 26 that revise previously published orbits, thus providing a significant update to the observed dynamics of M dwarfs in the solar neighborhood. From these orbits, we provide new and updated dynamical total masses for these systems, precise to 0.7%–7% in nearly all cases. Future mass derivations for components in these systems will contribute to efforts in refining the mass–luminosity relation for the smallest stars and will enhance investigations of age, magnetism, and metallicity effects on luminosities at a given mass.
Keywords: Brightness; Interferometry; Metallicity; Radial velocity; Solar System; Speckle imaging; Speckle pattern; Stars; dept.phy

The three-dimensional orbit and physical properties of the binary COU 2031 (WDS 04464+4221, HIP 22196, HD 30090) - Docobo, Jose Angel; Griffin, R F; Tamazian, V S; Horch, Elliott P; Campo, P P (Monthly Notices of the Royal Astronomical Society, 2014)
We report a comprehensive study of the binary system COU 2031, based on simultaneous and independent astrometric visual and speckle observations and on radial-velocity measurements. The similarity of the two orbital solutions allows us to obtain not only a consistent 3D orbit and a precise value of the parallax of the system but also to determine the physical properties of the components. © 2014 The Authors.
5 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/132-132-335-733-638 tex.type: [object Object]
Keywords: Binaries: spectroscopic; Binaries: visual; Stars: individual: COU 2031; dept.phy; peer-reviewed

Speckle camera observations for the NASA kepler mission follow-up program - Howell, Steve B; Everett, Mark E; Sherry, William Henry; Horch, Elliott P; Ciardi, David R (The Astronomical Journal, 2011)
We present the first results from a speckle imaging survey of stars classified as candidate exoplanet host stars discovered by the Kepler mission. We use speckle imaging to search for faint companions or closely aligned background stars that could contribute flux to the Kepler light curves of their brighter neighbors. Background stars are expected to contribute significantly to the pool of false positive candidate transiting exoplanets discovered by the Kepler mission, especially in the case that the faint neighbors are eclipsing binary stars. Here, we describe our Kepler follow-up observing program, the speckle imaging camera used, our data reduction, and astrometric and photometric performance. Kepler stars range from R = 8 to 16 and our observations attempt to provide background non-detection limits 5-6mag fainter and binary separations of ∼0.05-2.0 arcsec. We present data describing the relative brightness, separation, and position angles for secondary sources, as well as relative plate limits for non-detection of faint nearby stars around each of 156 target stars. Faint neighbors were found near 10 of the stars. © 2011. The American Astronomical Society. All rights reserved.
247 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/073-270-251-734-729 tex.type: [object Object]
Keywords: dept.phy; instrumentation: high angular resolution; peer-reviewed; planets and satellites: general; techniques: photometric

Observations of binary stars with the differential speckle survey instrument. III. measures below the diffraction limit of the WIYN telescope - Horch, Elliott P.; van Altena, William F.; Howell, Steve B.; Sherry, William Henry; Ciardi, David R. (The Astronomical Journal, 2011)
In this paper, we study the ability of CCD- and electron-multiplying-CCD- based speckle imaging to obtain reliable astrometry and photometry of binary stars below the diffraction limit of the WIYN 3.5 m Telescope. We present a total of 120 measures of binary stars, 75 of which are below the diffraction limit. The measures are divided into two groups that have different measurement accuracy and precision. The first group is composed of standard speckle observations, that is, a sequence of speckle images taken in a single filter, while the second group consists of paired observations where the two observations are taken on the same observing run and in different filters. The more recent paired observations were taken simultaneously with the Differential Speckle Survey Instrument, which is a two-channel speckle imaging system. In comparing our results to the ephemeris positions of binaries with known orbits, we find that paired observations provide the opportunity to identify cases of systematic error in separation below the diffraction limit and after removing these from consideration, we obtain a linear measurement uncertainty of 3-4 mas. However, if observations are unpaired or if two observations taken in the same filter are paired, it becomes harder to identify cases of systematic error, presumably because the largest source of this error is residual atmospheric dispersion, which is color dependent. When observations are unpaired, we find that it is unwise to report separations below approximately 20 mas, as these are most susceptible to this effect. Using the final results obtained, we are able to update two older orbits in the literature and present preliminary orbits for three systems that were discovered by Hipparcos. © 2011. The American Astronomical Society. All rights reserved..
28 citations (Crossref) [2023-10-31] Citation Key Alias: pop00076 tex.type: [object Object]
Keywords: binaries: visual; dept.phy; peer-reviewed; techniques: high angular resolution; techniques: interferometric; techniques: photometric

The WIYN Speckle Survey: Toward the Thin and Thick Disk Binary Populations - Horch, Elliott P.; van Altena, William F.; Docobo, J. A.; Tamazian, V. S.; Balega, Y. Y. (International Workshop on Double and Multiple Stars: Dynamics, Physics, and Instrumentation, 2011)
The WIYN Observatory speckle program has been in operation since 1997, taking data mainly with a large-format, low-noise CCD detector. However, new instrumentation, first used in 2008, has created the possibility to use two detectors simultaneously, collecting light in two different filters. The program also now has access to two electron-multiplying CCD cameras, which dramatically improve the limiting magnitude of the diffraction-limited imaging capabilities. The application of this instrumentation to an ongoing survey of the Hipparcos Double Stars and other projects is discussed. © 2011 American Institute of Physics.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/013-059-287-895-92X, pop00174 tex.number: [object Object]
Keywords: binaries: visual; dept.phy; stars: stellar populations; techniques: high angular resolution; techniques: interferometric; techniques: photometric

Charge-coupled device speckle observations of binary stars with the WIYN telescope. v. measures during 2001-2006 - Horch, Elliott P.; van Altena, William F.; Cyr, William M.; Kinsman-Smith, Lori; Srivastava, Amit; Zhou, Jing (The Astronomical Journal, 2008)
A total of 1067 speckle observations of 345 binary stars are presented. Of these, 161 are double stars first resolved by Hipparcos, 17 are resolved for the first time in the observations presented here, and 21 are stars previously discovered by our program and reported in earlier papers in the series. In 947 cases, a magnitude difference is reported along with the relative astrometry. When comparing to systems with very well-known orbits, we find that the root mean square (rms) deviation in separation residuals is 2.81 0.28 mas, and the rms deviation in position angle residuals is 0.88 0.07°. The magnitude difference measures show no significant deviation from Hipparcos photometry, and have average standard deviation of approximately 0.10 mag as judged from repeat observations. Five important systems discovered by Hipparcos are discussed. © 2008. The American Astronomical Society. All rights reserved..
56 citations (Crossref) [2023-10-31] Citation Key Alias: pop00069 tex.type: [object Object]
Keywords: Astrometry; Binaries: visual; Techniques: interferometric; Techniques: photometric; dept.phy; peer-reviewed

A Comprehensive Astrometric Calibration of HST's WFPC2. I. Distortion Mapping - Casetti-Dinescu, Dana I.; Girard, Terrence M.; Kozhurina-Platais, Vera; Platais, Imants; Anderson, Jay; Horch, Elliott P. (Publications of the Astronomical Society of the Pacific, 2021)
Wide field planetary camera 2 (WFPC2) exposures are already some 20 years older than Gaia epoch observations, or future James Webb Space Telescope observations. As such, they offer an unprecedented time baseline for high-precision proper-motion studies, provided the full astrometric potential of these exposures is reached. We have started such a project with the work presented here being its first step. We explore geometric distortions beyond the well-known ones published in the early 2000 s. This task is accomplished by using the entire database of WFPC2 exposures in filters F555W, F606W and F814W and three standard astrometric catalogs: Gaia EDR3, 47 Tuc and ωCen. The latter two were constructed using Hubble Space Telescope observations made with cameras other than WFPC2. We explore a suite of centering algorithms, and various distortion maps in order to understand and quantify their performance. We find no high-frequency systematics beyond the 34th-row correction, down to a resolution of 10 pixels. Low-frequency systematics starting at a resolution of 50 pixels are present at a level of 30–50 millipix (1.4–2.3 mas) for the PC and 20–30 millipix (2–3 mas) for the WF chips. We characterize these low-frequency systematics by providing correction maps and updated cubic-distortion coefficients for each filter.
3 citations (Crossref) [2023-10-31]
Keywords: dept.mat; dept.phy; peer-reviewed

Exclusion of stellar companions to exoplanet host stars - Wittrock, Justin M.; Kane, Stephen R.; Horch, Elliott P.; Howell, Steve B.; Ciardi, David R.; Everett, Mark E. (The Astronomical Journal, 2017)
Given the frequency of stellar multiplicity in the solar neighborhood, it is important to study the impacts this can have on exoplanet properties and orbital dynamics. There have been numerous imaging survey projects established to detect possible low-mass stellar companions to exoplanet host stars. Here, we provide the results from a systematic speckle imaging survey of known exoplanet host stars. In total, 71 stars were observed at 692 and 880 nm bands using the Differential Speckle Survey Instrument at the Gemini-north Observatory. Our results show that all but two of the stars included in this sample have no evidence of stellar companions with luminosities down to the detection and projected separation limits of our instrumentation. The mass-luminosity relationship is used to estimate the maximum mass a stellar companion can have without being detected. These results are used to discuss the potential for further radial velocity follow-up and interpretation of companion signals. © 2017. The American Astronomical Society. All rights reserved..
9 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/064-303-042-496-092, pop00140 tex.type: [object Object]
Keywords: dept.phy; peer-reviewed; planetary systems; techniques: high angular resolution

Prospects for wireless optical intensity interferometry with the Southern Connecticut stellar interferometer - Horch, Elliott P.; Weiss, Samuel A.; Rupert, Justin D.; LaRue, Ryan; Peronio, Pietro; Rech, Ivan; Gulinatti, Angelo (Optical and Infrared Interferometry and Imaging VI, 2018)
The Southern Connecticut Stellar Interferometer (SCSI) is a two-telescope astronomical intensity interferometer that was completed in June 2016 and has been taking photon correlation data since that time. It uses single-photon avalanche diode (SPAD) detectors at the telescope focal plane and a central timing module, which records the signals from both telescopes simultaneously. In the observations taken to date, single-pixel SPADs have been connected to signal cables that stretch from each telescope to the timing module. However, we are now in the process of making the instrument “wireless” by using a separate timing module at each telescope and synchronizing the signals recorded using GPS timing cards. We have also upgraded one of the two stations with an 8-pixel SPAD device, which allows us to achieve higher count rates in a variety of observing conditions. In this paper, we report on the current state of the instrument, including engineering tests made in preparation for wireless operation, and we discuss the expected capabilities in that mode.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/009-838-080-681-906, pop00166 tex.type: [object Object]
Keywords: Avalanche diodes; Engineering tests; Hanbury Brown and Twiss effect; Intensity interferometry; Interferometers; Interferometry; Particle beams; Photon correlation; Photons; Single photon avalanche diode; Stars; Stellar interferometers; Telescopes; Timing module; Wireless operation; Wireless-optical; dept.phy; single-photon avalanche diode (SPAD) detectors; timing correlation

Orbits of 14 binaries based on 2018 SOAR speckle observations - Docobo, José A; Gomez, Jorge; Campo, Pedro P; Andrade, Manuel; Horch, Elliott P; Costa, Edgardo; Mendez, Rene A (Monthly Notices of the Royal Astronomical Society, 2019)
New data obtained during the 2018 March-April speckle run at the 4.1 m Southern Astrophysical Research (SOAR) telescope located at Cerro Pachón (Chile) allowed us to recalculate the orbits of the following visual binaries: WDS 06478+0020 (STT 157),WDS 07003-2207 (FIN 334Aa,Ab), WDS 07013-0906 (A 671), WDS 10174-5354 (CVN 16Aa,Ab), WDS 12155-3106 (RST 1658),WDS 12572+0818 (FIN 380),WDS 13044-1316 (HU 642),WDS 14243-3838 (RST 1785), WDS 16094-3103 (I 557), WDS 17115-1630 (HU 169), WDS 17119-0151 (LPM 629),WDS 17563 + 0259 (A 2189),WDS 18464-2755 (RST 2073), and WDS 19035-6845 (FIN 357). All but three of them are Southern stars. The recently published Gaia parallaxes were used to calculate the total mass of each of these systems, despite the fact that, in a few cases, only Hipparcos parallaxes were available. For two binaries, A 671 and RST 2073, there are no parallax data. However, in these cases, the masses deduced from the dynamical parallaxes provided relevant information. In addition, we also present the first orbit for each of three systems: HU 642, RST 1785, and RST 2073, using speckle measurements. Finally, using the dynamical parallaxes given by these orbits, we have been able to calculate the luminosity of these systems. Said luminosities allow us to indicate an approximate age for each of the components of the system, situating them within the HR diagram. © 2018 The Author(s) Published by Oxford University Press on behalf of the Royal Astronomical Society.
7 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/024-727-074-773-961, pop00143 tex.type: [object Object]
Keywords: Techniques: high angular resolution - astrometry - binaries; Visual - stars: fundamental parameters; dept.phy; peer-reviewed

Observations of binary stars with the differential speckle survey instrument. VI. Measures during 2014 at the Discovery Channel Telescope - Horch, Elliott P.; van Belle, Gerard T.; Davidson, James W.; Ciastko, Lindsay A.; Everett, Mark E.; Bjorkman, Karen S. (The Astronomical Journal, 2015)
We present the results of 938 speckle measures of double stars and suspected double stars drawn mainly from the Hipparcos Catalog, as well as 208 observations where no companion was noted. One hundred fourteen pairs have been resolved for the first time. The data were obtained during four observing runs in 2014 using the Differential Speckle Survey Instrument at Lowell Observatory's Discovery Channel Telescope. The measurement precision obtained when comparing to ephemeris positions of binaries with very well-known orbits is generally less than 2 mas in separation and 0.°5 in position angle. Differential photometry is found to have internal precision of approximately 0.1 mag and to be in very good agreement with Hipparcos measures in cases where the comparison is most relevant. We also estimate the detection limit in the cases where no companion was found. Visual orbital elements are derived for six systems. © 2015. The American Astronomical Society. All rights reserved.
53 citations (Crossref) [2023-10-31] Citation Key Alias: pop00059 tex.type: [object Object]
Keywords: astrometry; binaries: visual; dept.phy; peer-reviewed; techniques: interferometric; techniques: photometric

Observations of binary stars with the differential speckle survey instrument. i. instrument description and first results - Horch, Elliott P.; Veillette, Daniel R.; Gallé, Roberto Baena; Shah, Sagar C.; O'Rielly, Grant; van Altena, William F. (The Astronomical Journal, 2009)
First results of a new speckle imaging system, the Differential Speckle Survey Instrument, are reported. The instrument is designed to take speckle data in two filters simultaneously with two independent CCD imagers. This feature results in three advantages over other speckle cameras: (1) twice as many frames can be obtained in the same observation time which can increase the signal-to-noise ratio for astrometric measurements, (2) component colors can be derived from a single observation, and (3) the two colors give substantial leverage over atmospheric dispersion, allowing for subdiffraction-limited separations to be measured reliably. Fifty-four observations are reported from the first use of the instrument at the Wisconsin-Indiana-Yale-NOAO 3.5 m Telescope9The WIYN Observatory is a joint facility of the University of Wisconsin-Madison, Indiana University, Yale University, and the National Optical Astronomy Observatories. in 2008 September, including seven components resolved for the first time. These observations are used to judge the basic capabilities of the instrument. © 2009. The American Astronomical Society. All rights reserved.
99 citations (Crossref) [2023-10-31] Citation Key Alias: pop00033 tex.type: [object Object]
Keywords: astrometry; binaries: close; binaries: visual; dept.phy; instrumentation: high angular resolution; instrumentation: interferometers; peer-reviewed; techniques: high angular resolution; techniques: interferometric; techniques: photometric

Orbits of M Dwarf Binaries Big and Small: Revealing Their Sizes and Shapes Via a Multi-Pronged Observing Campaign - Vrijmoet, Eliot; Henry, Todd; Tokovinin, Andrei; Dieterich, Serge; Horch, Elliott; Jao, Wei-Chun; Winters, Jennifer; Team, Recons (Bulletin of the American Astronomical Society, 2022)
Presentation #205.10 in the session Binary Stellar System - iPoster Session.
Keywords: dept.phy; ⛔ No DOI found

The Solar Neighborhood. LII. M Dwarf Twin Binaries—Presumed Identical Twins Appear Fraternal in Variability, Rotation, Hα, and X-Rays - Couperus, Andrew A.; Henry, Todd J.; Osten, Rachel A.; Jao, Wei-Chun; Vrijmoet, Eliot Halley; Kar, Aman; Horch, Elliott (The Astronomical Journal, 2024)
We present an investigation into the rotation and stellar activity of four fully convective M dwarf “twin” wide binaries. Components in each pair have (1) astrometry confirming they are common-proper-motion binaries, (2) Gaia BP, RP, and 2MASS J, H, and K s magnitudes matching within 0.10 mag, and (3) presumably the same age and composition. We report long-term photometry, rotation periods, multiepoch Hα equivalent widths, X-ray luminosities, time series radial velocities, and speckle observations for all components. Although it might be expected for the twin components to have matching magnetic attributes, this is not the case. Decade-long photometry of GJ 1183 AB indicates consistently higher spot activity on A than B, a trend matched by A appearing 58% ± 9% stronger in L X and 26% ± 9% stronger in Hα on average—this is despite similar rotation periods of A = 0.86 day and B = 0.68 day, thereby informing the range in activity for otherwise identical and similarly rotating M dwarfs. The young β Pic Moving Group member 2MA 0201+0117 AB displays a consistently more active B component that is 3.6 ± 0.5 times stronger in L X and 52% ± 19% stronger in Hα on average, with distinct rotation at A = 6.01 days and B = 3.30 days. Finally, NLTT 44989 AB displays remarkable differences with implications for spindown evolution—B has sustained Hα emission while A shows absorption, and B is ≥39 ± 4 times stronger in L X, presumably stemming from the surprisingly different rotation periods of A = 38 days and B = 6.55 days. The last system, KX Com, has an unresolved radial velocity companion, and is therefore not a twin system.
Keywords: dept.phy; peer-reviewed

Speckle imaging excludes low-mass companions orbiting the exoplanet host star trappist-1 - Howell, Steve B; Everett, Mark E; Horch, Elliott P; Winters, Jennifer G; Hirsch, Lea A; Nusdeo, Dan; Scott, Nicholas J (The Astrophysical Journal, 2016)
We have obtained the highest-resolution images available of TRAPPIST-1 using the Gemini-South telescope and our speckle imaging camera. Observing at 692 and 883 nm, we reached the diffraction limit of the telescope providing a best resolution of 27 mas or, at the distance of TRAPPIST-1, a spatial resolution of 0.32 au. Our imaging of the star extends from 0.32 to 14.5 au. We show that to a high confidence level, we can exclude all possible stellar and brown dwarf companions, indicating that TRAPPIST-1 is a single star. © 2016. The American Astronomical Society. All rights reserved.
45 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/135-678-895-243-534 tex.type: [object Object]
Keywords: dept.phy; stars: imaging; stars: individual (TRAPPIST-1; 2MASS J23062928-0502285)

High-resolution multi-band imaging for validation and characterization of small kepler planets - Everett, Mark E.; Barclay, Thomas; Ciardi, David R.; Horch, Elliott P.; Howell, Steve B.; Crepp, Justin R.; Silva, David R. (The Astronomical Journal, 2015)
High-resolution ground-based optical speckle and near-infrared adaptive optics images are taken to search for stars in close angular proximity to host stars of candidate planets identi fied by the NASA Kepler Mission. Neighboring stars are a potential source of false positive signals. These stars also blend into Kepler light curves, affecting estimated planet properties, and are important for an understanding of planets in multiple star systems. Deep images with high angular resolution help to validate candidate planets by excluding potential background eclipsing binaries as the source of the transit signals. A study of 18 Kepler Object of Interest stars hosting a total of 28 candidate and validated planets is presented. Validation levels are determined for 18 planets against the likelihood of a false positive from a background eclipsing binary. Most of these are validated at the 99% level or higher, including five newly validated planets in two systems: Kepler-430 and Kepler-431. The stellar properties of the candidate host stars are determined by supplementing existing literature values with new spectroscopic characterizations. Close neighbors of seven of these stars are examined using multi-wavelength photometry to determine their nature and influence on the candidate planet properties. Most of the close neighbors appear to be gravitationally bound secondaries, while a few are best explained as closely co-aligned field stars. Revised planet properties are derived for each candidate and validated planet, including cases where the close neighbors are the potential host stars. © 2015. The American Astronomical Society. All rights reserved.
46 citations (Crossref) [2023-10-31] Citation Key Alias: pop00061 tex.type: [object Object]
Keywords: Binaries: visual; Planetary systems; Planets and satellites: detection; Planets and satellites: fundamental parameters; Surveys; Techniques: high angular resolution; dept.phy; peer-reviewed

Ccd speckle observations of binary stars with the wiyn telescope. vi. measures during 2007-2008 - Horch, Elliott P.; Falta, David; Anderson, Lisa M.; DeSousa, Michael D.; Miniter, Craig M.; Ahmed, Tasmia; van Altena, William F. (The Astronomical Journal, 2009)
Results of 974 speckle observations of 546 binary stars are presented. Observations were obtained at the WIYN 3.5 m Telescope at Kitt Peak National Observatory during the time interval from 2007 January to 2008 June. In all cases, the relative separation and position angle of the components are measured, and the magnitude difference is determined in 809 cases. The precision of the results as judged from repeat observations and objects with very well-determined orbits is similar to previous papers in this series, namely ∼ 3 mas in separation and <1° in position angle in most cases. Similarly, the photometric precision remains consistent with previous WIYN speckle data, on average ∼ 0.1 mag per observation. Six systems of special interest are discussed. © 2010. The American Astronomical Society. All rights reserved.
58 citations (Crossref) [2023-10-31] Citation Key Alias: pop00066 tex.type: [object Object]
Keywords: Binaries: visual; Techniques: high angular resolution; Techniques: interferometric; Techniques:Photometric; dept.phy; peer-reviewed

Observations of Binary Stars with the Differential Speckle Survey Instrument. II. Hipparcos Stars Observed in 2010 January and June - Horch, Elliott P.; Gomez, Shamilia C.; Sherry, William Henry; Howell, Steve B.; Ciardi, David R.; Anderson, Lisa M.; van Altena, William F. (The Astronomical Journal, 2011)
The results of 497 speckle observations of Hipparcos stars and selected other targets are presented. Of these, 367 were resolved into components and 130 were unresolved. The data were obtained using the Differential Speckle Survey Instrument at the WIYN 3.5 m Telescope. (The WIYN Observatory is a joint facility of the University of Wisconsin-Madison, Indiana University, YaleUniversity, and theNational Optical AstronomyObservatories.) Since the first paper in this series, the instrument has been upgraded so that it now uses two electron-multiplying CCD cameras. The measurement precision obtained when comparing to ephemeris positions of binaries with very well known orbits is approximately 1-2 mas in separation and better than 0.̊ 6 in position angle. Differential photometry is found to be in very good agreement with Hipparcos measures in cases where the comparison is most relevant. We derive preliminary orbits for two systems. © 2011. The American Astronomical Society.
88 citations (Crossref) [2023-10-31] Citation Key Alias: pop00029 tex.type: [object Object]
Keywords: Binaries: Visual; Techniques: High angular resolution; Techniques: Interferometric; Techniques: Photometric; dept.phy; peer-reviewed

Discovery of a compact companion to a nearby star - Kane, Stephen R.; Dalba, Paul A.; Horner, Jonathan; Li, Zhexing; Wittenmyer, Robert A.; Horch, Elliott P.; Howell, Steve B.; Everett, Mark E. (The Astrophysical Journal, 2019)
Radial velocity (RV) searches for exoplanets have surveyed many of the nearest and brightest stars for long-term velocity variations indicative of a companion body. Such surveys often detect high-amplitude velocity signatures of objects that lie outside the planetary mass regime, most commonly those of a low-mass star. Such stellar companions are frequently discarded as false-alarms to the main science goals of the survey, but high-resolution imaging techniques can be employed to either directly detect or place significant constraints on the nature of the companion object. Here, we present the discovery of a compact companion to the nearby star HD 118475. Our Anglo-Australian Telescope RV data allow the extraction of the full Keplerian orbit of the companion, which is found to have a minimum mass of 0.445 M o. Follow-up speckle imaging observations at the predicted time of maximum angular separation rule out a main-sequence star as the source of the RV signature at the 3.3σ significance level, implying that the companion must be a low-luminosity compact object, most likely a white dwarf. We provide an isochrone analysis combined with our data that constrain the possible inclinations of the binary orbit. We discuss the eccentric orbit of the companion in the context of tidal circularization timescales and show that non-circular orbit was likely inherited from the progenitor. Finally, we emphasize the need for utilizing such an observation method to further understand the demographics of white dwarf companions around nearby stars. © 2019. The American Astronomical Society. All rights reserved.
7 citations (Crossref) [2023-10-31]
Keywords: dept.phy; stars: individual (HD 118475); techniques: high angular resolution; techniques: radial velocities; white dwarfs

Speckle Observations of Binary Stars with the Wiyn Telescope. Vii. Measures During 2008-2009 - Horch, Elliott P.; Bahi, Lizzie Anne P.; Gaulin, Joseph R.; Howell, Steve B.; Sherry, William Henry; Gallé, Roberto Baena; van Altena, William F. (The Astronomical Journal, 2011)
Five hundred thirty-one speckle measures of binary stars are reported. These data were taken mainly during the period 2008 June through 2009 October at the WIYN 3.5m Telescope at Kitt Peak and represent the last data set of single-filter speckle observations taken in the WIYN speckle program prior to the use of the current two-channel speckle camera. The astrometric and photometric precision of these observations is consistent with previous papers in this series: we obtain a typical linear measurement uncertainty of approximately 2.5mas, and the magnitude differences reported have typical uncertainties in the range of 0.1-0.14 mag. In combination with measures already in the literature, the data presented here permit the revision of the orbit of A 1634AB (= HIP 76041) and the first determination of visual orbital elements for HDS 1895 (= HIP 65982).
43 citations (Crossref) [2023-10-31] Citation Key Alias: pop00075 tex.type: [object Object]
Keywords: binaries: visual; dept.phy; peer-reviewed; techniques: high angular resolution; techniques: interferometric; techniques: photometric

Identifying bound stellar companions to kepler exoplanet host stars using speckle imaging - Colton, Nicole M.; Horch, Elliott P; Everett, Mark E; Howell, Steve B; Davidson, James W., Jr.; Baptista, Brian J.; Casetti-Dinescu, Dana I (Astronomical Journal, 2021)
The Kepler mission and subsequent ground-based follow-up observations have revealed a number of exoplanet host stars with nearby stellar companions. This study presents speckle observations of 57 Kepler objects of interest (KOIs) that are also double stars, each observed over a 3-8 yr period, which has allowed us to track their relative motions with high precision. Measuring the position angle and separation of the companion with respect to the primary can help determine if the pair exhibits common proper motion, indicating it is likely to be a bound binary system. We report on the motions of 34 KOIs that have close stellar companions, three of which are triple stars, for a total of 37 companions studied. Eighteen of the 34 systems are confirmed exoplanet hosts, including one triple star, while four other systems have been subsequently judged to be false positives and twelve are yet to be confirmed as planet hosts. We find that 21 are most likely to be common proper motion pairs, 4 are line-of-sight companions, and 12 are of an uncertain disposition at present. The fraction of the confirmed exoplanet host systems that are common proper motion pairs is approximately 86% in this sample. In this subsample, the planets are exclusively found with periods of less than 110 days, so that in all cases the stellar companion is found at a much larger separation from the planet host star than the planet itself. A preliminary period-radius relation for the confirmed planets in our sample suggests no obvious differences at this stage with the full sample of known exoplanets. © 2020. The American Astronomical Society. All rights reserved.
10 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85098523712
Keywords: dept.phy; peer-reviewed

SCSI: the southern connecticut stellar interferometer - Horch, Elliott P; Weiss, Samuel A; Rupert, Justin D; Dimaio, Alex J; Nusdeo, Daniel A; Peronio, Pietro; Rech, Ivan; Gulinatti, Angelo; Giudice, Andrea (Proceedings of SPIE, 2016)
The construction of a new prototype visible-light intensity interferometer for use in stellar astronomy is described. The instrument is located in New Haven, Connecticut, at Southern Connecticut State University, but key components of the system are also portable and have been taken to existing research-class telescopes to maximize sensitivity and baseline. The interferometer is currently a two-station instrument, but it is easily expandable to several stations for simultaneous measurement using multiple baselines. The design features single photon avalanche diode (SPAD) arrays, which increase the throughput and signal-To-noise ratio of the instrument. Predicted system performance and preliminary observations will be discussed. © 2016 SPIE.
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/071-922-688-145-060 tex.type: [object Object]
Keywords: Avalanche diodes; Design features; Intensity Interferometry; Interferometers; Interferometry; Particle beams; Photon Counting; Photon counting; Photons; Signal to noise ratio; Simultaneous measurement; Single Photon Avalanche Diode Arrays; Single photon avalanche diode; Single-photon avalanche diode arrays; Stars; Stellar interferometers; Timing Correlation; Ultra-High-Resolution Astronomy; Ultrahigh resolution; Visible light; dept.phy

Stellar companions to the exoplanet host stars HD 2638 and HD 164509 - Wittrock, Justin M; Kane, Stephen R; Horch, Elliott P; Hirsch, Lea A; Howell, Steve B; Ciardi, David R; Everett, Mark E; Teske, Johanna K (The Astronomical Journal, 2016)
An important aspect of searching for exoplanets is understanding the binarity of the host stars. It is particularly important, because nearly half of the solar-like stars within our own Milky Way are part of binary or multiple systems. Moreover, the presence of two or more stars within a system can place further constraints on planetary formation, evolution, and orbital dynamics. As part of our survey of almost a hundred host stars, we obtained images at 692 and 880 nm bands using the Differential Speckle Survey Instrument (DSSI) at the Gemini-North Observatory. From our survey, we detect stellar companions to HD-2638 and HD-164509. The stellar companion to HD-2638 has been previously detected, but the companion to HD-164509 is a newly discovered companion. The angular separation for HD-2638 is 0.512±0 002 and for HD-164509 is 0.697 0. 00 ' 2. This corresponds to a projected separation of 25.6±1.9 au and 36.5±1.9 au, respectively. By employing stellar isochrone models, we estimate the mass of the stellar companions of HD-2638 and HD-164509 to be 0.483±0.007-Me and 0.416 0.007 M, respectively, and their effective temperatures to be 3570±8K and 3450±7K, respectively. These results are consistent with the detected companions being late-type M dwarfs. © 2016. The American Astronomical Society. All rights reserved.
12 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/006-023-747-811-953 tex.type: [object Object]
Keywords: dept.phy; peer-reviewed; planetary systems; stars: individual (HD 2638; HD 164509); techniques: high angular resolution

Speckle observations of TESS exoplanet host stars: Understanding the binary exoplanet host star orbital period distribution - Howell, Steve B; Matson, Rachel A.; Ciardi, David R; Everett, Mark E; Livingston, John H.; Scott, Nicholas J; Horch, Elliott P; Winn, Joshua N (Astronomical Journal, 2021)
We present high-resolution speckle interferometric imaging observations of TESS exoplanet host stars using the NN-EXPLORE Exoplanet and Stellar Speckle Imager instrument at the 3.5 m WIYN telescope. Eight TESS objects of interest that were originally discovered by Kepler were previously observed using the Differential Speckle Survey Instrument. Speckle observations of 186 TESS stars were carried out, and 45 (24%) likely bound companions were detected. This is approximately the number of companions we would expect to observe given the established 46% binarity rate in exoplanet host stars. For the detected binaries, the distribution of stellar mass ratio is consistent with that of the standard Raghavan distribution and may show a decrease in high-q systems as the binary separation increases. The distribution of binary orbital periods, however, is not consistent with the standard Ragahavan model, and our observations support the premise that exoplanet-hosting stars with binary companions have, in general, wider orbital separations than field binaries. We find that exoplanet-hosting binary star systems show a distribution peaking near 100 au, higher than the 40–50 au peak that is observed for field binaries. This fact led to earlier suggestions that planet formation is suppressed in close binaries.
24 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85102449269
Keywords: dept.phy; peer-reviewed

Limits on stellar companions to exoplanet host stars with eccentric planets - Kane, Stephen R; Howell, Steve B; Horch, Elliott P; Feng, Ying; Hinkel, Natalie R; Ciardi, David R; Everett, Mark E; Howard, Andrew W; Wright, Jason T (The Astrophysical Journal, 2014)
Though there are now many hundreds of confirmed exoplanets known, the binarity of exoplanet host stars is not well understood. This is particularly true of host stars that harbor a giant planet in a highly eccentric orbit since these are more likely to have had a dramatic dynamical history that transferred angular momentum to the planet. Here we present observations of four exoplanet host stars that utilize the excellent resolving power of the Differential Speckle Survey Instrument on the Gemini North telescope. Two of the stars are giants and two are dwarfs. Each star is host to a giant planet with an orbital eccentricity >0.5 and whose radial velocity (RV) data contain a trend in the residuals to the Keplerian orbit fit. These observations rule out stellar companions 4-8 mag fainter than the host star at passbands of 692 nm and 880 nm. The resolution and field of view of the instrument result in exclusion radii of 0.″05-1.″4, which excludes stellar companions within several AU of the host star in most cases. We further provide new RVs for the HD 4203 system that confirm that the linear trend previously observed in the residuals is due to an additional planet. These results place dynamical constraints on the source of the planet's eccentricities, place constraints on additional planetary companions, and inform the known distribution of multiplicity amongst exoplanet host stars. © 2014. The American Astronomical Society. All rights reserved..
24 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/031-289-457-778-141 tex.type: [object Object]
Keywords: dept.phy; planetary systems; stars: individual (HD 4203; HD 168443; HD 1690; HD 137759); techniques: Radial velocities; techniques: high angular resolution

The RKSTAR Concert — A RECONS Survey of the 5000 Nearest K Dwarfs - Henry, Todd; Casetti-Dinescu, Dana; Horch, Elliott; Hubbard-James, Hodari-Sadiki; Jao, Wei-Chun; Lesley, D. Xavier; Paredes, Leonardo; Shea, Melissa; Sutherland, Torrie; Team, Recons (Bulletin of the American Astronomical Society, 2022)
Presentation #305.15 in the session Stars, Cool Dwarfs, Brown Dwarfs — iPoster Session.
Keywords: dept.phy; ⛔ No DOI found

Characterizing TESS-identified Quadruple- and Higher-order Eclipsing Binaries. I. Speckle Imaging with DSSI and HRCam - Majewski, Steven; Davidson, James; Wilson, Robert; Horch, Elliott; McKee, P.; Fagan, Evan; Hartwell, Gary; Kostov, Veselin; Adams, C.; Sutherland, Torrie; Tokovinin, Andreï; Wilson, John (The Astrophysical Journal, 2025)
Abstract NASA’s TESS mission has unveiled a plethora of eclipsing binaries (EBs), among them hundreds of triples and higher-order, hierarchical systems. These complex targets require follow-up observations to enable full characterization of system architectures and identify the most compact multiples expected to undergo the most dramatic dynamical evolution. We report first results from a long-term effort to perform such follow-up, focusing here on multiband speckle imaging of a majority (57) of the sample of 97 quadruple- and higher-order eclipsing binaries (Q+EBs) identified via TESS light curves by V. B. Kostov et al. Diffraction-limited imaging with the Differential Speckle Survey Instrument on the Astrophysical Research Consortium 3.5 m telescope and HRCam on the Southern Astrophysical Research 4.1 m telescope reveals nearly 60% of the 57 to resolve into two sources separated by ≥0 . ″ 03. For these partly resolved systems, we report derived characteristics (e.g., relative position angle, angular separation, and magnitude differences in multiple passbands) from the speckle imaging. We find those Q+EBs partly resolved with 4 m class telescopes to have significantly inflated Gaia parallax errors and large Gaia renormalized unit weight errors, particularly for systems with separations comparable to Gaia’s resolution limit (∼0 . ″ 6). For unresolved systems we report upper limits on angular and linear projected separations. We find two partly resolved Q+EBs with wide linear separations having eclipse timing variations that are therefore candidates of higher-than-quadruple multiplicity. Finally, we demonstrate how speckle imaging of resolved Q+EBs during an eclipse can clarify which speckle-resolved Q+EB subsystem is associated with a particular set of TESS eclipses.
Keywords: Angular resolution (graph drawing); Astrometry; Eclipse; Parallax; Speckle imaging; Speckle pattern; Telescope; dept.phy

Observations of binary stars with the differential speckle survey instrument. V. toward an empirical metal-poor mass–luminosity relation - Horch, Elliott P; Altena, William F Van; Demarque, Pierre; Howell, Steve B; Everett, Mark E; Ciardi, David R; Teske, Johanna K; Henry, Todd J; Winters, Jennifer G (The Astronomical Journal, 2015)
In an effort to better understand the details of the stellar structure and evolution of metal-poor stars, the Gemini North telescope was used on two occasions to take speckle imaging data of a sample of known spectroscopic binary stars and other nearby stars in order to search for and resolve close companions. The observations were obtained using the Differential Speckle Survey Instrument, which takes data in two filters simultaneously. The results presented here are of 90 observations of 23 systems in which one or more companions was detected, and six stars where no companion was detected to the limit of the camera capabilities at Gemini. In the case of the binary and multiple stars, these results are then further analyzed to make first orbit determinations in five cases, and orbit refinements in four other cases. The mass information is derived, and since the systems span a range in metallicity, a study is presented that compares our results with the expected trend in total mass as derived from the most recent Yale isochrones as a function of metal abundance. These data suggest that metal-poor main-sequence stars are less massive at a given color than their solar-metallicity analogues in a manner consistent with that predicted from the theory. © 2015. The American Astronomical Society. All rights reserved..
25 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/014-359-698-007-676 tex.type: [object Object]
Keywords: astrometry; binaries: visual; dept.phy; peer-reviewed; techniques: high angular resolution; techniques: interferometric; techniques: photometric

Kepler observations of three pre-launch exoplanet candidates: discovery of two eclipsing binaries and a new exoplanet - Howell, Steve Bruce; Rowe, Jason F.; Sherry, William; von Braun, Kaspar; Ciardi, David R.; Bryson, Stephen T.; Feldmeier, John J.; Horch, Elliott P.; van Belle, Gerard T. (The Astrophysical Journal, 2010)
Three transiting exoplanet candidate stars were discovered in a ground-based photometric survey prior to the launch of NASA's Kepler mission. Kepler observations of them were obtained during Quarter 1 of the Kepler mission. All three stars are faint by radial velocity follow-up standards, so we have examined these candidates with regard to eliminating false positives and providing high confidence exoplanet selection.We present a first attempt to exclude false positives for this set of faint stars without high-resolution radial velocity analysis. This method of exoplanet confirmation will form a large part of the Kepler mission follow-up for Jupiter-sized exoplanet candidates orbiting faint stars. Using the Kepler light curves and pixel data, as well as medium-resolution reconnaissance spectroscopy and speckle imaging, we find that two of our candidates are binary stars. One consists of a late-F star with an early M companion, while the other is a K0 star plus a late M-dwarf/brown dwarf in a 19 day elliptical orbit. The third candidate (BOKS-1) is an r = 15 G8V star hosting a newly discovered exoplanet with a radius of 1.12 RJupiter in a 3.9 day orbit. © 2010 The American Astronomical Society. All rights reserved.
12 citations (Crossref) [2023-10-31] Citation Key Alias: pop00072 tex.type: [object Object]
Keywords: Binaries: eclipsing; Brown dwarfs; Planetary systems; dept.phy

Assessing the effect of stellar companions from high-resolution imaging of Kepler objects of interest - Hirsch, Lea A.; Ciardi, David R.; Howard, Andrew W.; Everett, Mark E.; Furlan, Elise; Saylors, Mindy; Horch, Elliott P.; Howell, Steve B.; Teske, Johanna; Marcy, Geoffrey W. (The Astronomical Journal, 2017)
We report on 176 close (<2″) stellar companions detected with high-resolution imaging near 170 hosts of Kepler Objects of Interest (KOIs). These Kepler targets were prioritized for imaging follow-up based on the presence of small planets, so most of the KOIs in these systems (176 out of 204) have nominal radii <6 . Each KOI in our sample was observed in at least two filters with adaptive optics, speckle imaging, lucky imaging, or the Hubble Space Telescope. Multi-filter photometry provides color information on the companions, allowing us to constrain their stellar properties and assess the probability that the companions are physically bound. We find that 60%-80% of companions within 1″ are bound, and the bound fraction is >90% for companions within 0.″5; the bound fraction decreases with increasing angular separation. This picture is consistent with simulations of the binary and background stellar populations in the Kepler field. We also reassess the planet radii in these systems, converting the observed differential magnitudes to a contamination in the Kepler bandpass and calculating the planet radius correction factor, X R = R p(true)/R p(single). Under the assumption that planets in bound binaries are equally likely to orbit the primary or secondary, we find a mean radius correction factor for planets in stellar multiples of X R = 1.65. If stellar multiplicity in the Kepler field is similar to the solar neighborhood, then nearly half of all Kepler planets may have radii underestimated by an average of 65%, unless vetted using high-resolution imaging or spectroscopy. © 2017. The American Astronomical Society. All rights reserved.
49 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/119-135-164-854-429, pop00043 tex.type: [object Object]
Keywords: binaries: visual; dept.phy; peer-reviewed; planets and satellites: detection; planets and satellites: fundamental parameters; techniques: high angular resolution; techniques: photometric

Speckle imaging characterization of radial velocity exoplanet systems - Dalba, Paul A.; Kane, Stephen R.; Howell, Steve B; Horch, Elliott P; Li, Zhexing; Hirsch, Lea A.; Burt, Jennifer; Brandt, Timothy D.; Močnik, Teo; Henry, Gregory W. (Astronomical Journal, 2021)
We conducted speckle imaging observations of 53 stellar systems that were members of long-term radial velocity (RV) monitoring campaigns and exhibited substantial accelerations indicative of planetary or stellar companions in wide orbits. Our observations were made with blue and red filters using the Differential Speckle Survey Instrument at Gemini-South and the NN-Explore Exoplanet Stellar Speckle Imager at the WIYN telescope. The speckle imaging identifies eight luminous companions within 2" of the primary stars. In three of these systems-HD 1388, HD 87359, and HD 104304-the properties of the imaged companion are consistent with the RV measurements, suggesting that these companions may be associated with the primary and the cause of the RV variation. For all 53 stellar systems, we derive differential magnitude limits (i.e., contrast curves) from the imaging. We extend this analysis to include upper limits on companion mass in systems without imaging detections. In 25 systems, we rule out companions with masses greater than 0.2 M⊙, suggesting that the observed RV signals are caused by late-M dwarfs or substellar (potentially planetary) objects. On the other hand, the joint RV and imaging analysis almost entirely rules out planetary explanations of the RV signal for HD 19522 and suggests that the companion must have an angular separation below a few tenths of an arcsecond. This work highlights the importance of combined RV and imaging observations for characterizing the outer regions of nearby planetary systems. © 2021 Institute of Physics Publishing. All rights reserved.
5 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85101618449
Keywords: dept.phy; peer-reviewed

The POKEMON Speckle Survey of nearby M Dwarfs. II. Observations of 1125 targets - Clark, Catherine A.; Belle, Gerard T. van; Horch, Elliott P.; Lund, Michael B.; Ciardi, David R.; Braun, Kaspar von; Winters, Jennifer G.; Everett, Mark E.; Hartman, Zachary D.; Llama, Joe (The Astronomical Journal, 2024)
Stellar multiplicity is correlated with many stellar properties, yet multiplicity measurements have proven difficult for the M dwarfs—the most common type of star in our galaxy—due to their faintness and the fact that a reasonably complete inventory of later M dwarfs did not exist until recently. We have therefore carried out the Pervasive Overview of “Kompanions” of Every M dwarf in Our Neighborhood (POKEMON) survey, which made use of the Differential Speckle Survey Instrument on the 4.3 m Lowell Discovery Telescope, along with the NN-EXPLORE Exoplanet Stellar Speckle Imager on the 3.5 m WIYN telescope. The POKEMON sample is volume limited from M0V through M9V out to 15 pc, with additional brighter targets at larger distances. In total, 1125 targets were observed. New discoveries were presented in the first paper in the series. In this second paper in the series, we present all detected companions, gauge our astrometric and photometric precision, and compare our filtered and filterless speckle observations. We find that the majority (58.9%) of the companions we detect in our speckle images are not resolved in Gaia, demonstrating the need for high-resolution imaging in addition to long-term astrometric monitoring. Additionally, we find that the majority (73.2%) of simulated stellar companions would be detectable by our speckle observations. Specifically within 100 au, we find that 70.3% of simulated companions are recovered. Finally, we discuss future directions of the POKEMON survey.
Keywords: dept.phy; peer-reviewed

Dissecting the Quadruple Binary Hyad vA 351 Masses for Three M Dwarfs and a White Dwarf\ast - Benedict, G. Fritz; Franz, Otto G.; Horch, Elliott P.; Prato, L.; Torres, Guillermo; McArthur, Barbara E.; Wasserman, Lawrence H.; Latham, David W.; Stefanik, Robert P.; Latham, Christian; Skiff, Brian A. (The Astronomical Journal, 2021)
We extend results first announced by Franz et al., that identified vA 351 = H346 in the Hyades as a multiple star system containing a white dwarf. With Hubble Space Telescope Fine Guidance Sensor fringe tracking and scanning, and more recent speckle observations, all spanning 20.7 years, we establish a parallax, relative orbit, and mass fraction for two components, with a period, and total mass 2.1 . With ground-based radial velocities from the McDonald Observatory Otto Struve 2.1 m Telescope Sandiford Spectrograph, and Center for Astrophysics Digital Speedometers, spanning 37 years, we find that component B consists of BC, two M dwarf stars orbiting with a very short period ( days), having a mass ratio / = 0.95. We confirm that the total mass of the system can only be reconciled with the distance and component photometry by including a fainter, higher-mass component. The quadruple system consists of three M dwarfs (A, B, C) and one white dwarf (D). We determine individual M dwarf masses = 0.53 ± 0.10 , = 0.43 ± 0.04 , and = 0.41 ± 0.04 . The white dwarf mass, 0.54 ± 0.04 , comes from cooling models, an assumed Hyades age of 670 Myr, and consistency with all previous and derived astrometric, photometric, and radial velocity results. Velocities from Hα and He i emission lines confirm the BC period derived from absorption lines, with similar (He i) and higher (Hα) velocity amplitudes. We ascribe the larger Hα amplitude to emission from a region each component shadows from the other, depending on the line of sight.
1 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Observations with the differential speckle survey instrument. X. Preliminary orbits of k-dwarf binaries and other stars - Horch, Elliott P.; Broderick, Kyle G.; Casetti-Dinescu, Dana I.; Henry, Todd J.; Fekel, Francis C.; Muterspaugh, Matthew W.; Willmarth, Daryl W.; Winters, Jennifer G.; van Belle, Gerard T.; Clark, Catherine; Everett, Mark E. (The Astronomical Journal, 2021)
This paper details speckle observations of binary stars taken at the Lowell Discovery Telescope, the WIYN telescope, and the Gemini telescopes between 2016 January and 2019 September. The observations taken at Gemini and Lowell were done with the Differential Speckle Survey Instrument (DSSI), and those done at WIYN were taken with the successor instrument to DSSI at that site, the NN-EXPLORE Exoplanet Star and Speckle Imager (NESSI). In total, we present 378 observations of 178 systems, and we show that the uncertainty in the measurement precision for the combined data set is ∼2 mas in separation, ∼1°-2° in position angle depending on the separation, and ∼0.1 mag in magnitude difference. Together with data already in the literature, these new results permit 25 visual orbits and one spectroscopic-visual orbit to be calculated for the first time. In the case of the spectroscopic-visual analysis, which is done on the ternary star HD 173093, we calculate masses with a precision of better than 1% for all three stars in that system. Twenty-one of the visual orbits calculated have a K dwarf as the primary star; we add these to the known orbits of K-dwarf primary stars and discuss the basic orbital properties of these stars at this stage. Although incomplete, the data that exist so far indicate that binaries with K-dwarf primaries tend not to have low-eccentricity orbits at separations of one to a few tens of astronomical units, that is, on solar system scales. © 2021 Institute of Physics Publishing. All rights reserved.
6 citations (Crossref) [2023-10-31] https://par.nsf.gov/biblio/10296367-observations-differential-speckle-survey-instrument-preliminary-orbits-dwarf-binaries-other-stars ; https://ui.adsabs.harvard.edu/abs/2021AJ....161..295H/abstract ;
Keywords: dept.phy; peer-reviewed

Observations of binary stars with the Differential Speckle Survey Instrument. VII. Measures from 2010 September to 2012 February at the WIYN Telescope - Horch, Elliott P.; Casetti-Dinescu, Dana I.; Camarata, Matthew A.; Bidarian, Akbar; Altena, William F. van; Sherry, William H.; Everett, Mark E.; Howell, Steve B.; Ciardi, David R.; Henry, Todd J.; Nusdeo, Daniel A.; Winters, Jennifer G. (The Astronomical Journal, 2017)
We report on speckle observations of binary stars carried out at the WIYN Telescope over the period from 2010 September through 2012 February, providing relative astrometry for 2521 observations of 883 objects, 856 of which are double stars and 27 of which are triples. The separations measured span a range of 0.01-1.75 arcsec. Wavelengths of 562, 692, and 880 nm were used, and differential photometry at one or more of these wavelengths is presented in most cases. 66 components were resolved for the first time. We also estimate detection limits at 0.2 and 1.0 arcsec for high-quality observations in cases where no companion was seen, a total of 176 additional objects. Detection limits vary based on observing conditions and signal-to-noise ratio, but are approximately 4 mag at 0.2 arcsec and 6 mag at 1.0 arcsec on average. Analyzing the measurement precision of the data set, we find that the individual separations obtained have linear measurement uncertainties of approximately 2 mas, and photometry is uncertain to approximately 0.1 mag in general. This work provides fundamental, well-calibrated data for future orbit and mass determinations, and we present three first orbits and total mass estimates of nearby K-dwarf systems as examples of this potential. © 2017. The American Astronomical Society. All rights reserved..
55 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/110-417-913-195-546, pop00017 tex.type: [object Object]
Keywords: binaries: visual; dept.phy; peer-reviewed; techniques: high angular resolution; techniques: interferometric; techniques: photometric

Dynamical masses of young M dwarfs: masses and orbital parameters of gj 3305 ab, the wide binary companion to the imaged exoplanet host 51 eri - Montet, Benjamin T; Bowler, Brendan P; Shkolnik, Evgenya L; Deck, Katherine M; Wang, Ji; Horch, Elliott P; Liu, Michael C; Hillenbrand, Lynne A; Kraus, Adam L; Charbonneau, David; Hillenbrand, Lynne A; Kraus, Adam L; et al. (The Astrophysical Journal, 2015)
We combine new high resolution imaging and spectroscopy from Keck/NIRC2, Discovery Channel Telescope/DSSI, and Keck/HIRES with published astrometry and radial velocities to measure individual masses and orbital elements of the GJ 3305 AB system, a young (∼20 Myr) M+M binary (unresolved spectral type M0) member of the β Pictoris moving group comoving with the imaged exoplanet host 51 Eri. We measure a total system mass of 1.11 ± 0.04 , a period of 29.03 ± 0.50 year, a semimajor axis of 9.78 ± 0.14 AU, and an eccentricity of 0.19 ± 0.02. The primary component has a dynamical mass of 0.67 ± 0.05 and the secondary has a mass of 0.44 ± 0.05 . The recently updated BHAC15 models are consistent with the masses of both stars to within Given the observed masses the models predict an age of the GJ 3305 AB system of 37 ± 9 Myr. Based on the observed system architecture and our dynamical mass measurement, it is unlikely that the orbit of 51 Eri b has been significantly altered by the Kozai-Lidov mechanism. © 2015. The American Astronomical Society. All rights reserved..
42 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/082-123-910-981-94X tex.type: [object Object]
Keywords: astrometry; binaries: close; dept.phy; stars: fundamental parameters; stars: individual (GJ 3305 AB)

A quintuple star system containing two eclipsing binaries - Rappaport, S; Lehmann, H; Kalomeni, B; Borkovits, T; Latham, D W; Bieryla, Allyson; Ngo, Henry; Mawet, Dimitri; Howell, Steve B; Horch, Elliott P; Jacobs, T L; Lacourse, D; et al. (Monthly Notices of the Royal Astronomical Society, 2016)
We present a quintuple star system that contains two eclipsing binaries. The unusual architecture includes two stellar images separated by 11 arcsec on the sky: EPIC 212651213 and EPIC 212651234. The more easterly image (212651213) actually hosts both eclipsing binaries which are resolved within that image at 0.09 arcsec, while the westerly image (212651234) appears to be single in adaptive optics (AO), speckle imaging, and radial velocity (RV) studies. The 'A' binary is circular with a 5.1-d period, while the 'B' binary is eccentric with a 13.1-d period. The γ velocities of the A and B binaries are different by ~10 km s-1. That, coupled with their resolved projected separation of 0.09 arcsec, indicates that the orbital period and separation of the 'C' binary (consisting of A orbiting B) are ≃65 yr and ≃25 au, respectively, under the simplifying assumption of a circular orbit. Motion within the C orbit should be discernible via future RV, AO, and speckle imaging studies within a couple of years. The C system (i.e. 212651213) has an RV and proper motion that differ from that of 212651234 by only ~1.4 kms-1 and ~3 mas yr-1. This set of similar space velocities in three dimensions strongly implies that these two objects are also physically bound, making this at least a quintuple star system. © 2016 The Authors.
10 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/126-257-541-980-666 tex.type: [object Object]
Keywords: Binaries: close; Binaries: eclipsing; Binaries: general; Binaries: spectroscopic; Binaries: visual; dept.phy; peer-reviewed

Spitzer observations of gj 3470 b: a very low-density neptune-size planet orbiting a metal-rich m dwarf* - Demory, Brice-Olivier; Torres, Guillermo; Neves, V.; Rogers, Leslie A.; Gillon, Michaël; Horch, Elliott P.; Sullivan, Peter W.; Bonfils, Xavier; Delfosse, Xavier; Forveille, Thierry; Lovis, Christophe; Mayor, Michel; et al. (The Astrophysical Journal, 2013)
We present Spitzer/IRAC 4.5 μm transit photometry of GJ 3470 b, a Neptune-size planet orbiting an M1.5 dwarf star with a 3.3 day period recently discovered in the course of the HARPS M-dwarf survey. We refine the stellar parameters by employing purely empirical mass-luminosity and surface brightness relations constrained by our updated value for the mean stellar density, and additional information from new near-infrared spectroscopic observations. We derive a stellar mass of and a radius of of M* = 0.539 +0.047-0.043 M⊙ and a radius of R* = 0.568+0.037-0.031 R⊙. We determine the host star of GJ 3470 b to be metal-rich, with a metallicity of [Fe/H] = +0.20 ± 0.10 and an effective temperature of Teff = 3600 ± 100 K. The revised stellar parameters yield a planetary radius Rp= 4.83+0.22-0.21 R⊕that is 13% larger than the value previously reported in the literature. We find a planetary mass M p= 13.9+1.5-1.4 M⊕ that translates to a very low planetary density, ρp = 0.72+0.13 -0.12 g cm-3, which is 33% smaller than the original value. With a mean density half of that of GJ 436 b, GJ 3470 b is an example of a very low-density low-mass planet, similar to Kepler-11 d, Kepler-11 e, and Kepler-18 c, but orbiting a much brighter nearby star that is more conducive to follow-up studies. © 2013. The American Astronomical Society. All rights reserved.
29 citations (Crossref) [2023-10-31] Citation Key Alias: pop00035 tex.type: [object Object]
Keywords: dept.phy; planetary systems; stars: individual (GJ 3470); techniques: photometric; techniques: spectroscopic

Exoplanet characterization by proxy: A transiting 2.15 r ⊕ planet near the habitable zone of the late K dwarf Kepler-61 - Ballard, Sarah; Charbonneau, David; Fressin, Francois; Torres, Guillermo; Irwin, Jonathan; Desert, Jean-Michel; Newton, Elisabeth; Mann, Andrew W.; Ciardi, David R.; Crepp, Justin R.; Henze, Christopher E.; Bryson, Stephen T.; et al. (The Astrophysical Journal, 2013)
We present the validation and characterization of Kepler-61b: a 2.15 R ⊕ planet orbiting near the inner edge of the habitable zone of a low-mass star. Our characterization of the host star Kepler-61 is based upon a comparison with a set of spectroscopically similar stars with directly measured radii and temperatures. We apply a stellar prior drawn from the weighted mean of these properties, in tandem with the Kepler photometry, to infer a planetary radius for Kepler-61b of 2.15 ± 0.13 R ⊕ and an equilibrium temperature of 273 ± 13 K (given its period of 59.87756 ± 0.00020 days and assuming a planetary albedo of 0.3). The technique of leveraging the physical properties of nearby “proxy” stars allows for an independent check on stellar characterization via the traditional measurements with stellar spectra and evolutionary models. In this case, such a check had implications for the putative habitability of Kepler-61b: the planet is 10% warmer and larger than inferred from K-band spectral characterization. From the Kepler photometry, we estimate a stellar rotation period of 36 days, which implies a stellar age of >1 Gyr. We summarize the evidence for the planetary nature of the Kepler-61 transit signal, which we conclude is 30,000 times more likely to be due to a planet than a blend scenario. Finally, we discuss possible compositions for Kepler-61b with a comparison to theoretical models as well as to known exoplanets with similar radii and dynamically measured masses.
33 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/071-947-168-650-048, pop00052 tex.type: [object Object]
Keywords: dept.phy; eclipses; planetary systems; stars: individual (Kepler-61; KOI 1361; KIC 6960913)

The same frequency of planets inside and outside open clusters of stars. - Meibom, Soren; Torres, Guillermo; Fressin, Francois; Latham, David; Rowe, Jason; Ciardi, David; Bryson, Steven; Rogers, Leslie; Henze, Christopher; Janes, Kenneth; Barnes, Sydney; Marcy, Geoffrey; et al. (Nature, 2013)
: Most stars and their planets form in open clusters. Over 95 per cent of such clusters have stellar densities too low (less than a hundred stars per cubic parsec) to withstand internal and external dynamical stresses and fall apart within a few hundred million years 1. Older open clusters have survived by virtue of being richer and denser in stars (1,000 to 10,000 per cubic parsec) when they formed. Such clusters represent a stellar environment very different from the birthplace of the Sun and other planet-hosting field stars. So far more than 800 planets have been found around Sun-like stars in the field 2. The field planets are usually the size of Neptune or smaller 3,4,5. In contrast, only four planets have been found orbiting stars in open clusters 6,7,8, all with masses similar to or greater than that of Jupiter. Here we report observations of the transits of two Sun-like stars by planets smaller than Neptune in the billion-year-old open cluster NGC6811. This demonstrates that small planets can form and survive in a dense cluster environment, and implies that the frequency and properties of planets in open clusters are consistent with those of planets around field stars in the Galaxy., (C) 2013 Nature Publishing Group
84 citations (Crossref) [2023-10-31] Place: (C) 2013 Nature Publishing Group
Keywords: Jupiter; Neptune; article; astronomy; cluster analysis; dept.phy; environment; frequency analysis; planet; priority journal; simulation; sun; velocity

Four sub-Saturns with dissimilar densities: Windows into planetary cores and envelopes - Petigura, Erik A.; Sinukoff, Evan; Lopez, Eric D.; Crossfield, Ian J. M.; Howard, Andrew W.; Brewer, John M.; Fulton, Benjamin J.; Isaacson, Howard T.; Ciardi, David R.; Howell, Steve B.; Everett, Mark E.; Horch, Elliott P.; et al. (The Astronomical Journal, 2017)
We present results from a Keck/HIRES radial velocity campaign to study four sub-Saturn-sized planets, K2-27b, K2-32b, K2-39b, and K2-108b, with the goal of understanding their masses, orbits, and heavy-element enrichment. The planets have similar sizes (RP=4.5-5.5 ), but have dissimilar masses (MP=16-60 ), implying a diversity in their core and envelope masses. K2-32b is the least massive (MP = 16.5 ± 2.7 M) and orbits in close proximity to two sub-Neptunes near a 3:2:1 period commensurability. K2-27b and K2-39b are significantly more massive at MP = 30.9 ± 4.6 M and MP = 39.8 ± 4.4 M, respectively, and show no signs of additional planets. K2-108b is the most massive at MP = 59.4 ± 4.4 M, implying a large reservoir of heavy elements of about ≈50 . Sub-Saturns as a population have a large diversity in planet mass at a given size. They exhibit remarkably little correlation between mass and size; sub-Saturns range from ≈6-60 M, regardless of size. We find a strong correlation between planet mass and host star metallicity, suggesting that metal-rich disks form more massive planet cores. The most massive sub-Saturns tend to lack detected companions and have moderately eccentric orbits, perhaps as a result of a previous epoch of dynamical instability. Finally, we observe only a weak correlation between the planet envelope fraction and present-day equilibrium temperature, suggesting that photo-evaporation does not play a dominant role in determining the amount of gas sub-Saturns accrete from their protoplanetary disks. © 2017. The American Astronomical Society. All rights reserved..
62 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/117-273-244-483-27X, pop00045 tex.type: [object Object]
Keywords: dept.phy; peer-reviewed; planets and satellites: composition; planets and satellites: detection; planets and satellites: dynamical evolution and stability; planets and satellites: formation; planets and satellites: gaseous planets; planets and satellites: interiors

Characterizing K2 candidate planetary systems orbiting Low-mass stars. II. Planetary Systems observed during campaigns 1–7 - Dressing, Courtney D.; Vanderburg, Andrew; Schlieder, Joshua E.; Crossfield, Ian J. M.; Knutson, Heather A.; Newton, Elisabeth R.; Ciardi, David R.; Fulton, Benjamin J.; Gonzales, Erica J.; Howard, Andrew W.; Isaacson, Howard; Livingston, John; et al. (The Astronomical Journal, 2017)
We recently used near-infrared spectroscopy to improve the characterization of 76 low-mass stars around which K2 had detected 79 candidate transiting planets. 29 of these worlds were new discoveries that had not previously been published. We calculate the false positive probabilities that the transit-like signals are actually caused by non-planetary astrophysical phenomena and reject five new transit-like events and three previously reported events as false positives. We also statistically validate 17 planets (7 of which were previously unpublished), confirm the earlier validation of 22 planets, and announce 17 newly discovered planet candidates. Revising the properties of the associated planet candidates based on the updated host star characteristics and refitting the transit photometry, we find that our sample contains 21 planets or planet candidates with radii smaller than 1.25 R ⊕, 18 super-Earths (1.25-2 R ⊕), 21 small Neptunes (2-4 R ⊕), three large Neptunes (4-6 R ⊕), and eight giant planets (>6 R ⊕). Most of these planets are highly irradiated, but EPIC 206209135.04 (K2-72e, ), EPIC 211988320.01 (), and EPIC 212690867.01 () orbit within optimistic habitable zone boundaries set by the "recent Venus" inner limit and the "early Mars" outer limit. In total, our planet sample includes eight moderately irradiated 1.5-3 R ⊕ planet candidates (F p ≲ 20 F ⊕) orbiting brighter stars (Ks < 11) that are well-suited for atmospheric investigations with the Hubble, Spitzer, and/or James Webb Space Telescopes. Five validated planets orbit relatively bright stars (Kp < 12.5) and are expected to yield radial velocity semi-amplitudes of at least 2 m s-1. Accordingly, they are possible targets for radial velocity mass measurement with current facilities or the upcoming generation of red optical and near-infrared high-precision RV spectrographs. © 2017. The American Astronomical Society. All rights reserved..
68 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed; planetary systems; planets and satellites: fundamental parameters; stars: fundamental parameters; stars: late-type; stars: low-mass; techniques: spectroscopic

Detection of planetary and stellar companions to neighboring stars via a combination of radial velocity and direct imaging techniques - Kane, Stephen R.; Dalba, Paul A.; Li, Zhexing; Horch, Elliott P.; Hirsch, Lea A.; Horner, Jonathan; Wittenmyer, Robert A.; Howell, Steve B.; Everett, Mark E.; Butler, R. Paul; Tinney, Christopher G.; Carter, Brad D.; et al. (The Astronomical Journal, 2019)
The sensitivities of radial velocity (RV) surveys for exoplanet detection are extending to increasingly longer orbital periods, where companions with periods of several years are now being regularly discovered. Companions with orbital periods that exceed the duration of the survey manifest in the data as an incomplete orbit or linear trend, a feature that can either present as the sole detectable companion to the host star, or as an additional signal overlain on the signatures of previously discovered companion(s). A diagnostic that can confirm or constrain scenarios in which the trend is caused by an unseen stellar rather than planetary companion is the use of high-contrast imaging observations. Here, we present RV data from the Anglo-Australian Planet Search (AAPS) for 20 stars that show evidence of orbiting companions. Of these, six companions have resolved orbits, with three that lie in the planetary regime. Two of these (HD 92987b and HD 221420b) are new discoveries. Follow-up observations using the Differential Speckle Survey Instrument (DSSI) on the Gemini South telescope revealed that 5 of the 20 monitored companions are likely stellar in nature. We use the sensitivity of the AAPS and DSSI data to place constraints on the mass of the companions for the remaining systems. Our analysis shows that a planetary-mass companion provides the most likely self-consistent explanation of the data for many of the remaining systems.
27 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/016-295-956-723-177, pop00041 tex.type: [object Object]
Keywords: dept.phy; peer-reviewed; planetary systems; techniques: high angular resolution; techniques: radial velocities

Observations of binary stars with the differential speckle survey instrument. IX. Observations of known and suspected binaries, and a partial survey of be stars - Horch, Elliott P.; van Belle, Gerard T.; Davidson, James W., Jr.; Willmarth, Daryl; Fekel, Francis C.; Muterspaugh, Matthew; Casetti-Dinescu, Dana I.; Hahne, Frederick W.; Granucci, Nicole M.; Clark, Catherine; Winters, Jennifer G.; Rupert, Justin D.; et al. (The Astronomical Journal, 2020)
We report 370 measures of 170 components of binary and multiple-star systems, obtained from speckle imaging observations made with the Differential Speckle Survey Instrument at Lowell Observatory's Discovery Channel Telescope in 2015 through 2017. Of the systems studied, 147 are binary stars, 10 are seen as triple systems, and 1 quadruple system is measured. Seventy-six high-quality nondetections and 15 newly resolved components are presented in our observations. The uncertainty in relative astrometry appears to be similar to our previous work at Lowell, namely, linear measurement uncertainties of approximately 2 mas, and the relative photometry appears to be uncertain at the 0.1-0.15 mag level. Using these measures and those in the literature, we calculate six new visual orbits, including one for the Be star 66 Oph and two combined spectroscopic-visual orbits. The latter two orbits, which are for HD 22451 (YSC 127) and HD 185501 (YSC 135), yield individual masses of the components at the level of 2% or better, and independent distance measures that in one case agrees with the value found in the Gaia DR2 and in the other disagrees at the 2σ level. We find that HD 22451 consists of an F6V+F7V pair with orbital period of 2401.1 ± 3.2 days and masses of 1.342 ± 0.029 and 1.236 ± 0.026M⊙. For HD 185501, both stars are G5 dwarfs that orbit one another with a period of 433.94 ± 0.15 days, and the masses are 0.898 ± 0.012 and 0.876 ± 0.012M⊙ . We discuss the details of both the new discoveries and the orbit objects. © 2020. The American Astronomical Society. All rights reserved..
17 citations (Crossref) [2023-10-31] tex.ids: horchObservationsBinaryStars2020a tex.adsnote: Provided by the SAO/NASA Astrophysics Data System tex.adsurl: https://ui.adsabs.harvard.edu/abs/2020AJ....159..233H arXiv: 2004.03065 [astro-ph.SR] tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85086596087 tex.eid: 233 type: Article
Keywords: Astrophysics - Earth and Planetary Astrophysics; Astrophysics - Instrumentation and Methods for Astrophysics; Astrophysics - Solar and Stellar Astrophysics; dept.phy; peer-reviewed

Two new long-period giant planets from the McDonald observatory planet search and two stars with long-period radial velocity signals related to stellar activity cycles - Endl, Michael; Brugamyer, Erik; Cochran, William D.; MacQueen, Phillip J.; Robertson, Paul; Meschiari, Stefano; Ramirez, Ivan; Shetrone, Matthew D.; Gullikson, Kevin; Johnson, Marshall C.; Wittenmyer, Robert A.; Horner, Jonathan; et al. (The Astrophysical Journal, 2016)
We report the detection of two new long-period giant planets orbiting the stars HD 95872 and HD 162004 (φ1 Dra B) by the McDonald Observatory planet search. The planet HD 95872b has a minimum mass of 4.6 MJup and an orbital semimajor axis of 5.2 AU. The giant planet φ1 Dra Bb has a minimum mass of 1.5 MJup and an orbital semimajor axis of 4.4 AU. Both of these planets qualify as Jupiter analogs. These results are based on over one and a half decades of precise radial velocity (RV) measurements collected by our program using the McDonald Observatory Tull Coude spectrograph at the 2.7 m Harlan J. Smith Telescope. In the case of φ1 Dra B we also detect a long-term nonlinear trend in our data that indicates the presence of an additional giant planet, similar to the Jupiter-Saturn pair. The primary of the binary star system, φ1 Dra A, exhibits a very large amplitude RV variation due to another stellar companion. We detect this additional member using speckle imaging. We also report two cases - HD 10086 and HD 102870 (β Virginis) - of significant RV variation consistent with the presence of a planet, but that are probably caused by stellar activity, rather than reflexive Keplerian motion. These two cases stress the importance of monitoring the magnetic activity level of a target star, as long-term activity cycles can mimic the presence of a Jupiter-analog planet. © 2016. The American Astronomical Society. All rights reserved.
30 citations (Crossref) [2023-10-31] Citation Key Alias: pop00073 tex.type: [object Object]
Keywords: dept.phy; planetary systems; stars: activity; techniques: radial velocities

Zodiacal Exoplanets in Time (ZEIT). VII. A temperate candidate Super-Earth in the Hyades Cluster - Vanderburg, Andrew; Mann, Andrew W.; Rizzuto, Aaron; Bieryla, Allyson; Kraus, Adam L.; Berlind, Perry; Calkins, Michael L.; Curtis, Jason L.; Douglas, Stephanie T.; Esquerdo, Gilbert A.; Everett, Mark E.; Horch, Elliott P.; et al. (The Astronomical Journal, 2018)
Transiting exoplanets in young open clusters present opportunities to study how exoplanets evolve over their lifetimes. Recently, significant progress detecting transiting planets in young open clusters has been made with the K2 mission, but so far all of these transiting cluster planets orbit close to their host stars, so planet evolution can only be studied in a high-irradiation regime. Here, we report the discovery of a long-period planet candidate, called HD 283869 b, orbiting a member of the Hyades cluster. Using data from the K2 mission, we detected a single transit of a super-Earth-sized (1.96 0.12 R ⊕) planet candidate orbiting the K-dwarf HD 283869 with a period longer than 72 days. As we only detected a single-transit event, we cannot validate HD 283869 b with high confidence, but our analysis of the K2 images, archival data, and follow-up observations suggests that the source of the event is indeed a transiting planet. We estimated the candidate's orbital parameters and find that if real, it has a period P ≈ 100 days and receives approximately Earth-like incident flux, giving the candidate a 71% chance of falling within the circumstellar habitable zone. If confirmed, HD 283869 b would have the longest orbital period, lowest incident flux, and brightest host star of any known transiting planet in an open cluster, making it uniquely important to future studies of how stellar irradiation affects planetary evolution. © 2018. The American Astronomical Society. All rights reserved..
32 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/008-063-848-375-694, pop00021 tex.type: [object Object]
Keywords: dept.phy; peer-reviewed; planetary systems; planets and satellites: detection; stars: individual (HD 283869)

An Earth-Sized Planet in the Habitable Zone of a Cool Star. - Quintana, Elisa; Barclay, Thomas; Raymond, Sean; Rowe, Jason; Bolmont, Emeline; Caldwell, Douglas; Howell, Steve; Kane, Stephen; Huber, Daniel; Crepp, Justin; Lissauer, Jack; Ciardi, David; et al. (Science, 2014)
The quest for Earth-like planets is a major focus of current exoplanet research. Although planets that are Earth-sized and smaller have been detected, these planets reside in orbits that are too close to their host star to allow liquid water on their surfaces. We present the detection of Kepler-186f, a 1.11 ± 0.14 Earth-radius planet that is the outermost of five planets, all roughly Earth-sized, that transit a 0.47 ± 0.05 solar-radius star. The intensity and spectrum of the star's radiation place Kepler-186f in the stellar habitable zone, implying that if Kepler-186f has an Earth-like atmosphere and water at its surface, then some of this water is likely to be in liquid form.
189 citations (Crossref) [2023-10-31] Place: Copyright (C) 2014 by the American Association for the Advancement of Science
Keywords: Earth; Earth (Planet); Exobiology; Extraterrestrial Environment; Planets; Stars; Celestial; Water; astrobiology; astronomy; atmosphere; cosmic radiation; dept.phy; habitat use; microclimate; priority journal; review; solar system; surface property; water

The mass of KOI-94d and a relation for planet radius, mass, and incident flux - Weiss, Lauren M.; Marcy, Geoffrey W.; Rowe, Jason F.; Howard, Andrew W.; Isaacson, Howard; Fortney, Jonathan J.; Miller, Neil; Demory, Brice-Olivier; Fischer, Debra A.; Adams, Elisabeth R.; Dupree, Andrea K.; Howell, Steve B.; et al. (The Astrophysical Journal, 2013)
We measure the mass of a modestly irradiated giant planet, KOI-94d. We wish to determine whether this planet, which is in a 22 day orbit and receives 2700 times as much incident flux as Jupiter, is as dense as Jupiter or rarefied like inflated hot Jupiters. KOI-94 also hosts at least three smaller transiting planets, all of which were detected by the Kepler mission. With 26 radial velocities of KOI-94 from the W. M. Keck Observatory and a simultaneous fit to the Kepler light curve, we measure the mass of the giant planet and determine that it is not inflated. Support for the planetary interpretation of the other three candidates comes from gravitational interactions through transit timing variations, the statistical robustness of multi-planet systems against false positives, and several lines of evidence that no other star resides within the photometric aperture. We report the properties of KOI-94b (M P = 10.5 ± 4.6 M ⊕, R P = 1.71 ± 0.16 R ⊕, P = 3.74 days), KOI-94c (M P = M ⊕, R P = 4.32 ± 0.41 R ⊕, P = 10.4 days), KOI-94d (M P = 106 ± 11 M ⊕, R P = 11.27 ± 1.06 R ⊕, P = 22.3 days), and KOI-94e (M P = M ⊕, R P = 6.56 ± 0.62 R ⊕, P = 54.3 days). The radial velocity analyses of KOI-94b and KOI-94e offer marginal (>2σ) mass detections, whereas the observations of KOI-94c offer only an upper limit to its mass. Using the KOI-94 system and other planets with published values for both mass and radius (138 exoplanets total, including 35 with M P < 150 M ⊕), we establish two fundamental planes for exoplanets that relate their mass, incident flux, and radius from a few Earth masses up to 13 Jupiter masses: (R P/R ⊕) = 1.78(M P/M ⊕)0.53(F/erg s–1 cm–2)–0.03 for M P < 150 M ⊕, and R P/R ⊕ = 2.45(M P/M ⊕)–0.039(F/erg s–1 cm–2)0.094 for M P > 150 M ⊕. These equations can be used to predict the radius or mass of a planet.
223 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/043-207-643-634-196, pop00005 tex.type: [object Object]
Keywords: dept.phy; planets and satellites: composition; techniques: photometric; techniques: spectroscopic

Observations of binary stars with the Differential Speckle Survey Instrument. VIII. Measures of metal-poor and triple stars from 2015 to 2018 - Horch, Elliott P.; Tokovinin, Andrei; Weiss, Samuel A.; Löbb, János; Casetti-Dinescu, Dana I.; Granucci, Nicole M.; Hess, Nicole M.; Everett, Mark E.; van Belle, Gerard T.; Winters, Jennifer G.; Nusdeo, Daniel A.; Henry, Todd J.; et al. (The Astronomical Journal, 2019)
We present 248 speckle observations of 43 binary and 19 trinary star systems chosen to make progress in two main areas of investigation: the fundamental properties of metal-poor stars and star formation mechanisms. The observations were taken at the Gemini North and South telescopes during the period 2015 July to 2018 April, mainly with the Differential Speckle Survey Instrument but also with a few early results from the new 'Alopeke speckle camera at Gemini North. We find that the astrometry and photometry of these observations as a whole are consistent with previous work at Gemini. We present five new visual orbits for systems important in understanding metal-poor stars, three of which have orbital periods of less than 4 yr, and we indicate the degree to which these and future observations can impact our knowledge of stellar properties and star formation. In particular, we find a decrease in mass at fixed spectral type for metal-poor stars versus their solar-metallicity analogs that is consistent with predictions that are made from current stellar models. © 2019. The American Astronomical Society. All rights reserved..
19 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/073-502-692-786-428, pop00025 tex.type: [object Object]
Keywords: binaries: visual; dept.phy; peer-reviewed; stars: individual; techniques: high angular resolution; techniques: interferometric; techniques: photometric

Validation of small Kepler transiting planet candidates in or near the habitable zone - Torres, Guillermo; Kane, Stephen R.; Rowe, Jason F.; Batalha, Natalie M.; Henze, Christopher E.; Ciardi, David R.; Barclay, Thomas; Borucki, William J.; Buchhave, Lars A.; Crepp, Justin R.; Everett, Mark E.; Horch, Elliott P.; et al. (The Astronomical Journal, 2017)
A main goal of NASA's Kepler Mission is to establish the frequency of potentially habitable Earth-size planets (). Relatively few such candidates identified by the mission can be confirmed to be rocky via dynamical measurement of their mass. Here we report an effort to validate 18 of them statistically using the BLENDER technique, by showing that the likelihood they are true planets is far greater than that of a false positive. Our analysis incorporates follow-up observations including high-resolution optical and near-infrared spectroscopy, high-resolution imaging, and information from the analysis of the flux centroids of the Kepler observations themselves. Although many of these candidates have been previously validated by others, the confidence levels reported typically ignore the possibility that the planet may transit a star different from the target along the same line of sight. If that were the case, a planet that appears small enough to be rocky may actually be considerably larger and therefore less interesting from the point of view of habitability. We take this into consideration here and are able to validate 15 of our candidates at a 99.73% (3σ) significance level or higher, and the other three at a slightly lower confidence. We characterize the GKM host stars using available ground-based observations and provide updated parameters for the planets, with sizes between 0.8 and 2.9 R ⊕. Seven of them (KOI-0438.02, 0463.01, 2418.01, 2626.01, 3282.01, 4036.01, and 5856.01) have a better than 50% chance of being smaller than 2 R ⊕ and being in the habitable zone of their host stars. © 2017. The American Astronomical Society. All rights reserved..
20 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/052-258-082-978-883, pop00029 tex.type: [object Object]
Keywords: dept.phy; methods: statistical; peer-reviewed; planetary systems; stars: individual (KOI-0172.02 = Kepler-69c ...); techniques: photometric

Observations with the Differential Speckle Survey Instrument. XI. First uear of observations from Apache Point Observatory - Davidson, James W.; Horch, Elliott P.; Majewski, Steven R.; Fagan, Evan; Shea, Melissa A.; Sutherland, Torrie; Wilson, Robert F.; Lesley, D. Xavier; Pellegrino, Richard A.; Leonard, Jonathan P.; Wilson, John C.; Chanover, Nancy J.; et al. (The Astronomical Journal, 2024)
The Differential Speckle Survey Instrument (DSSI) was relocated to the Astrophysical Research Consortium 3.5 m telescope at Apache Point Observatory (APO) in early 2022. Here we present results from the first year of observations along with an updated instrument description for DSSI at APO, including a detailed description of a new internal slit mask assembly used to measure the instrument plate scale from first principles. Astrometric precision for DSSI at APO during this time was measured to be 2.06 ± 0.11 mas, with a photometric precision of 0.14 ± 0.04 mag. Results of 40 resolved binary systems are reported, including two that were previously unknown to be binaries: HIP 7535 and HIP 9603. We also present updated orbital fits for two systems: HIP 93903 and HIP 100714. Finally, we report updated or confirmed dispositions for five Kepler Objects of Interest (KOIs) that were previously explored in Colton et al., using speckle imaging to discern common proper motions pairs from line of sight companions: KOI-270, KOI-959, KOI-1613, KOI-1962, and KOI-3214AB.
Keywords: dept.phy

The orbit and dynamical mass of polaris: Observations with the CHARA array - Evans, Nancy Remage; Schaefer, Gail H.; Gallenne, Alexandre; Torres, Guillermo; Horch, Elliott P.; Anderson, Richard I.; Monnier, John D.; Roettenbacher, Rachael M.; Baron, Fabien; Anugu, Narsireddy; Davidson, James W.; Kervella, Pierre; et al. (The Astrophysical Journal, 2024)
The 30 yr orbit of the Cepheid Polaris has been followed with observations by the Center for High Angular Resolution Astronomy (CHARA) Array from 2016 through 2021. An additional measurement has been made with speckle interferometry at the Apache Point Observatory. Detection of the companion is complicated by its comparative faintness—an extreme flux ratio. Angular diameter measurements appear to show some variation with pulsation phase. Astrometric positions of the companion were measured with a custom grid-based model-fitting procedure and confirmed with the CANDID software. These positions were combined with the extensive radial velocities (RVs) discussed by Torres to fit an orbit. Because of the imbalance of the sizes of the astrometry and RV data sets, several methods of weighting are discussed. The resulting mass of the Cepheid is 5.13 ± 0.28 M ⊙. Because of the comparatively large eccentricity of the orbit (0.63), the mass derived is sensitive to the value found for the eccentricity. The mass combined with the distance shows that the Cepheid is more luminous than predicted for this mass from evolutionary tracks. The identification of surface spots is discussed. This would give credence to the identification of a radial velocity variation with a period of approximately 120 days as a rotation period. Polaris has some unusual properties (rapid period change, a phase jump, variable amplitude, and unusual polarization). However, a pulsation scenario involving pulsation mode, orbital periastron passage, and low pulsation amplitude can explain these characteristics within the framework of pulsation seen in Cepheids.
Keywords: dept.phy; peer-reviewed

Three temperate neptunes orbiting nearby stars - Fulton, Benjamin J; Howard, Andrew W; Weiss, Lauren M; Sinukoff, Evan; Petigura, Erik A; Isaacson, Howard; Hirsch, Lea A; Marcy, Geoffrey W; Henry, Gregory W; Grunblatt, Samuel K; Huber, Daniel; Huber, Daniel; et al. (The Astrophysical Journal, 2016)
We present the discovery of three modestly irradiated, roughly Neptune-mass planets orbiting three nearby Solartype stars. HD 42618 b has a minimum mass of 15.4±2.4 M⊕, a semimajor axis of 0.55 au, an equilibrium temperature of 337 K, and is the first planet discovered to orbit the solar analogue host star, HD 42618. We also discover new planets orbiting the known exoplanet host stars HD 164922 and HD 143761 (p CrB). The new planet orbiting HD 164922 has a minimum mass of 12.9±1.6 M⊕ and orbits interior to the previously known Jovian mass planet orbiting at 2.1 au. HD 164922 c has a semimajor axis of 0.34 au and an equilibrium temperature of 418 K. HD 143761 c orbits with a semimajor axis of 0.44 au, has a minimum mass of 25±2 M⊕, and is the warmest of the three new planets with an equilibrium temperature of 445 K. It orbits exterior to the previously known warm Jupiter in the system. A transit search using space-based CoRoT data and ground-based photometry from the Automated Photometric Telescopes (APTs) at Fairborn Observatory failed to detect any transits, but the precise, high-cadence APT photometry helped to disentangle planetary-reflex motion from stellar activity. These planets were discovered as part of an ongoing radial velocity survey of bright, nearby, chromospherically inactive stars using the Automated Planet Finder (APF) telescope at Lick Observatory. The high-cadence APF data combined with nearly two decades of radial velocity data from Keck Observatory and gives unprecedented sensitivity to both short-period low-mass, and long-period intermediate-mass planets. © 2016. The American Astronomical Society. All rights reserved..
23 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/015-506-416-922-520 tex.type: [object Object]
Keywords: dept.phy; planetary systems; stars: individual (HD 42618; HD 164922; HD 143761)

Kepler-63b: A giant planet in a polar orbit around a young sun-like star - Sanchis-Ojeda, Roberto; Winn, Joshua N.; Marcy, Geoffrey W.; Howard, Andrew W.; Isaacson, Howard; Johnson, John Asher; Torres, Guillermo; Albrecht, Simon; Campante, Tiago L.; Chaplin, William J.; Davies, Guy R.; Lund, Mikkel N.; et al. (The Astrophysical Journal, 2013)
We present the discovery and characterization of a giant planet orbiting the young Sun-like star Kepler-63 (KOI-63, M⊙Kp = 11.6, T eff = 5576 K, M⊙ = 0.98 M⊙). The planet transits every 9.43 days, with apparent depth variations and brightening anomalies caused by large starspots. The planet's radius is 6.1 ± 0.2 R ⊕, based on the transit light curve and the estimated stellar parameters. The planet's mass could not be measured with the existing radial-velocity data, due to the high level of stellar activity, but if we assume a circular orbit, then we can place a rough upper bound of 120 M ⊙⊕ (3σ). The host star has a high obliquity (ψ = 104°), based on the Rossiter-McLaughlin effect and an analysis of starspot-crossing events. This result is valuable because almost all previous obliquity measurements are for stars with more massive planets and shorter-period orbits. In addition, the polar orbit of the planet combined with an analysis of spot-crossing events reveals a large and persistent polar starspot. Such spots have previously been inferred using Doppler tomography, and predicted in simulations of magnetic activity of young Sun-like stars. © 2013. The American Astronomical Society. All rights reserved..
98 citations (Crossref) [2023-10-31] Citation Key Alias: pop00012 tex.type: [object Object]
Keywords: dept.phy; planetary systems; stars: activity; stars: individual (Kepler-63); stars: rotation; starspots

K2 discovers a busy bee: an unusual transiting neptune found in the beehive cluster - Obermeier, Christian; Henning, Thomas; Schlieder, Joshua E.; Crossfield, Ian J. M.; Petigura, Erik A.; Howard, Andrew W.; Sinukoff, Evan; Isaacson, Howard; Ciardi, David R.; David, Trevor J.; Hillenbrand, Lynne A.; Beichman, Charles A.; et al. (The Astronomical Journal, 2016)
Open clusters have been the focus of several exoplanet surveys, but only a few planets have so far been discovered. The Kepler spacecraft revealed an abundance of small planets around small cool stars, therefore, such cluster members are prime targets for exoplanet transit searches. Kepler's new mission, K2, is targeting several open clusters and star-forming regions around the ecliptic to search for transiting planets around their low-mass constituents. Here, we report the discovery of the first transiting planet in the intermediate-age (800 Myr) Beehive cluster (Praesepe). K2-95 is a faint (Kp = 15.5 mag) dwarf from K2's Campaign 5 with an effective temperature of 3471 ±124 K, approximately solar metallicity and a radius of 0.402± 0.050.R⊕ We detected a transiting planet with a radius of3.47+0.78 -0.53R⊕ and an orbital period of 10.134 days. We combined photometry, medium/high-resolution spectroscopy, adaptive optics/speckle imaging, and archival survey images to rule out any false-positive detection scenarios, validate the planet, and further characterize the system. The planet's radius is very unusual as M-dwarf field stars rarely have Neptune-sized transiting planets. The comparatively large radius of K2-95b is consistent with the other recently discovered cluster planets K2-25b (Hyades) and K2-33b (Upper Scorpius), indicating systematic differences in their evolutionary states or formation. These discoveries from K2 provide a snapshot of planet formation and evolution in cluster environments and thus make excellent laboratories to test differences between field-star and cluster planet populations. © 2016. The American Astronomical Society. All rights reserved..
62 citations (Crossref) [2023-10-31] Citation Key Alias: pop00057 tex.type: [object Object]
Keywords: dept.phy; eclipses; peer-reviewed; stars: individual (K2-95); stars: low-mass; techniques: photometric; techniques: spectroscopic

HAT-P-68b: A transiting hot jupiter around a K5 dwarf star - Lindor, Bethlee M.; Hartman, Joel D.; Bakos, Gáspár Á.; Bhatti, Waqas; Csubry, Zoltan; Penev, Kaloyan; Bieryla, Allyson; Lathman, David W; Torres, Guillermo; Buchhave, Lars A; de Val-Borro, Miguel; Howard, Andrew W; et al. (Astronomical Journal, 2021)
We report the discovery by the ground-based Hungarian-made Automated Telescope Network (HATNet) survey of the transiting exoplanet HAT-P-68b, which has a mass of 0.724 ± 0.043 MJ, and radius of 1.072 ± 0.012 RJ. The planet is in a circular P = 2.2984 day orbit around a moderately bright V = 13.937 ± 0.030 magnitude K-dwarf star of mass ${0.673}_{-0.014}{+0.020}$ M⊙, and radius 0.6726 ± 0.0069 R⊙. The planetary nature of this system is confirmed through follow-up transit photometry obtained with the Fred L. Whipple Observatory (FLWO) 1.2 m telescope, high-precision radial velocities measured using Keck I/High Resolution Echelle Spectrometer (HIRES), FLWO 1.5 m/Tillinghast Reflector Echelle Spectrograph (TRES), and Observatoire de Haute-Provence (OHP) 1.9 m/Sophie, and high-spatial-resolution speckle imaging from WIYN 3.5 m/DSSI. HAT-P-68 is at an ecliptic latitude of +3° and outside the field of view of both the NASA Transiting Exoplanet Survey Satellite primary mission and the K2 mission. The large transit depth of 0.036 mag (r band) makes HAT-P-68b a promising target for atmospheric characterization via transmission spectroscopy.
2 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85101652867
Keywords: dept.phy; peer-reviewed

A seismic and gravitationally bound double star observed by Kepler - Appourchaux, T; Antia, H M; Ball, Warrick H; Creevey, O; Lebreton, Y; Verma, Kuldeep; Vorontsov, Sergei V; Campante, T L; Campante, T L; Davies, G R; Davies, G R; Gaulme, Patrick; et al. (Astronomy and Astrophysics, 2015)
Context. Solar-like oscillations have been observed by Kepler and CoRoT in many solar-type stars, thereby providing a way to probe stars using asteroseismology. Aims. The derivation of stellar parameters has usually been done with single stars. The aim of the paper is to derive the stellar parameters of a double-star system (HIP93511), for which an interferometric orbit has been observed along with asteroseismic measurements. Methods. We used a time series of nearly two years of data for the double star to detect the two oscillation-mode envelopes that appear in the power spectrum. Using a new scaling relation based on luminosity, we derived the radius and mass of each star. We derived the age of each star using two proxies: one based upon the large frequency separation and a new one based upon the small frequency separation. Using stellar modelling, the mode frequencies allowed us to derive the radius, the mass, and the age of each component. In addition, speckle interferometry performed since 2006 has enabled us to recover the orbit of the system and the total mass of the system. Results. From the determination of the orbit, the total mass of the system is 2.34-0.33 +0.45 M⊙. The total seismic mass using scaling relations is 2.47 ± 0.07 M⊙. The seismic age derived using the new proxy based upon the small frequency separation is 3.5 ± 0.3 Gyr. Based on stellar modelling, the mean common age of the system is 2.7-3.9 Gyr. The mean total seismic mass of the system is 2.34-2.53 M⊙ consistent with what we determined independently with the orbit. The stellar models provide the mean radius, mass, and age of the stars as RA = 1.82-1.87R⊙, MA = 1.25-1.39 M⊙, AgeA = 2.6-3.5 Gyr; RB = 1.22-1.25 R⊙, MB = 1.08-1.14 M⊙, AgeB = 3.35-4.21 Gyr. The models provide two sets of values for Star A: [1.25-1.27] M⊙ and [1.34-1.39] M⊙. We detect a convective core in Star A, while Star B does not have any. For the metallicity of the binary system of Z ≈ 0.02, we set the limit between stars having a convective core in the range [1.14-1.25] M⊙. © ESO, 2015.
42 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/000-480-656-795-885 tex.type: [object Object]
Keywords: Asteroseismology; Binaries: general; Interferometry; Orbits; Seismology; Separation; Speckle; Stars; Stars: evolution; Stars: solar types; asteroseismology; astrometry; binaries: general; dept.phy; stars: evolution; stars: solar-type

JWST/NIRCam 4–5 μm Imaging of the Giant Planet AF Lep b - Franson, Kyle; Balmer, William O.; Bowler, Brendan P.; Pueyo, Laurent; Zhou, Yifan; Rickman, Emily; Zhang, Zhoujian; Mukherjee, Sagnick; Pearce, Tim D.; Gagliuffi, Daniella C. Bardalez; Biddle, Lauren I.; Brandt, Timothy D.; et al. (The Astrophysical Journal Letters, 2024)
With a dynamical mass of 3 M Jup, the recently discovered giant planet AF Lep b is the lowest-mass imaged planet with a direct mass measurement. Its youth and spectral type near the L/T transition make it a promising target to study the impact of clouds and atmospheric chemistry at low surface gravities. In this work, we present JWST/NIRCam imaging of AF Lep b. Across two epochs, we detect AF Lep b in F444W (4.4 μm) with signal-to-noise ratios of 9.6 and 8.7, respectively. At the planet’s separation of 320 mas during the observations, the coronagraphic throughput is ≈7%, demonstrating that NIRCam’s excellent sensitivity persists down to small separations. The F444W photometry of AF Lep b affirms the presence of disequilibrium carbon chemistry and enhanced atmospheric metallicity. These observations also place deep limits on wider-separation planets in the system, ruling out 1.1 M Jup planets beyond 15.6 au (0.″58), 1.1 M Sat planets beyond 27 au (1″), and 2.8 M Nep planets beyond 67 au (2.″5). We also present new Keck/NIRC2 imaging of AF Lep b; combining this with the two epochs of F444W photometry and previous Keck photometry provides limits on the long-term 3–5 μm variability of AF Lep b on timescales of months to years. AF Lep b is the closest-separation planet imaged with JWST to date, demonstrating that planets can be recovered well inside the nominal (50% throughput) NIRCam coronagraph inner working angle.
Keywords: dept.phy

Validation of 12 small kepler transiting planets in the habitable zone - Torres, Guillermo; Kipping, David M; Fressin, Francois; Caldwell, Douglas A; Twicken, Joseph D; Ballard, Sarah; Batalha, Natalie M; Bryson, Stephen T; Ciardi, David R; Henze, Christopher E; Howell, Steve B; Isaacson, Howard; et al. (The Astrophysical Journal, 2015)
We present an investigation of 12 candidate transiting planets from Kepler with orbital periods ranging from 34 to 207 days, selected from initial indications that they are small and potentially in the habitable zone (HZ) of their parent stars. Few of these objects are known. The expected Doppler signals are too small to confirm them by demonstrating that their masses are in the planetary regime. Here we verify their planetary nature by validating them statistically using the BLENDER technique, which simulates large numbers of false positives and compares the resulting light curves with the Kepler photometry. This analysis was supplemented with new follow-up observations (high-resolution optical and near-infrared spectroscopy, adaptive optics imaging, and speckle interferometry), as well as an analysis of the flux centroids. For 11 of them (KOI-0571.05, 1422.04, 1422.05, 2529.02, 3255.01, 3284.01, 4005.01, 4087.01, 4622.01, 4742.01, and 4745.01) we show that the likelihood they are true planets is far greater than that of a false positive, to a confidence level of 99.73% (3σ) or higher. For KOI-4427.01 the confidence level is about 99.2% (2.6σ). With our accurate characterization of the GKM host stars, the derived planetary radii range from 1.1 to 2.7 R ⊕. All 12 objects are confirmed to be in the HZ, and nine are small enough to be rocky. Excluding three of them that have been previously validated by others, our study doubles the number of known rocky planets in the HZ. KOI-3284.01 (Kepler-438b) and KOI-4742.01 (Kepler-442b) are the planets most similar to the Earth discovered to date when considering their size and incident flux jointly. © 2015. The American Astronomical Society. All rights reserved..
94 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/036-512-292-095-617 tex.type: [object Object]
Keywords: dept.phy; methods: statistical; planetary systems; stars: individual (KOI-3284 (Kepler-438); KOI-4742 (Kepler-442)); techniques: photometric

275 candidates and 149 validated planets orbiting bright stars in K 2 campaigns 0–10 - Mayo, Andrew W.; Vanderburg, Andrew; Latham, David W.; Bieryla, Allyson; Morton, Timothy D.; Buchhave, Lars A.; Dressing, Courtney D.; Beichman, Charles; Berlind, Perry; Calkins, Michael L.; Ciardi, David R.; Crossfield, Ian J. M.; et al. (The Astronomical Journal, 2018)
Since 2014, NASA's K2 mission has observed large portions of the ecliptic plane in search of transiting planets and has detected hundreds of planet candidates. With observations planned until at least early 2018, K2 will continue to identify more planet candidates. We present here 275 planet candidates observed during Campaigns 0-10 of the K2 mission that are orbiting stars brighter than 13 mag (in Kepler band) and for which we have obtained high-resolution spectra (R = 44,000). These candidates are analyzed using the vespa package in order to calculate their false-positive probabilities (FPP). We find that 149 candidates are validated with an FPP lower than 0.1%, 39 of which were previously only candidates and 56 of which were previously undetected. The processes of data reduction, candidate identification, and statistical validation are described, and the demographics of the candidates and newly validated planets are explored. We show tentative evidence of a gap in the planet radius distribution of our candidate sample. Comparing our sample to the Kepler candidate sample investigated by Fulton et al., we conclude that more planets are required to quantitatively confirm the gap with K2 candidates or validated planets. This work, in addition to increasing the population of validated K2 planets by nearly 50% and providing new targets for follow-up observations, will also serve as a framework for validating candidates from upcoming K2 campaigns and the Transiting Exoplanet Survey Satellite, expected to launch in 2018. © 2018. The American Astronomical Society. All rights reserved.
114 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/061-080-708-221-69X, pop00001, pop00002 tex.type: [object Object]
Keywords: dept.phy; methods: data analysis; peer-reviewed; planets and satellites: detection; techniques: photometric

HAT-P-58b – HAT-P-64b: Seven planets transiting bright stars - Bakos, G. Á.; Hartman, Joel D.; Bhatti, Waqas; Csubry, Z.; Penev, Kaloyan; Bieryla, Allyson; Latham, D. W.; Quinn, S. N.; Buchhave, Lars A.; Kovács, Gábor L.; Torres, Guillermo; Noyes, R. W.; et al. (The Astronomical Journal, 2021)
We report the discovery and characterization of seven transiting exoplanets from the HATNet survey. The planets, which are hot Jupiters and Saturns transiting bright Sun-like stars, include: HAT-P-58b (with mass M p = 0.37 M J, radius R p = 1.33 R J, and orbital period P = 4.0138 days), HAT-P-59b (M p = 1.54 M J, R p = 1.12 R J, P = 4.1420 days), HAT-P-60b (M p = 0.57 M J, R p = 1.63 R J, P = 4.7948 days), HAT-P-61b (M p = 1.06 M J, R p = 0.90 R J, P = 1.9023 days), HAT-P-62b (M p = 0.76 M J, R p = 1.07 R J, P = 2.6453 days), HAT-P-63b (M p = 0.61 M J, R p = 1.12 R J, P = 3.3777 days), and HAT-P-64b (M p = 0.58 M J, R p = 1.70 R J, P = 4.0072 days). The typical errors on these quantities are 0.06 M J, 0.03 R J, and 0.2 s, respectively. We also provide accurate stellar parameters for each of the host stars. With V = 9.710 0.050 mag, HAT-P-60 is an especially bright transiting planet host, and an excellent target for additional follow-up observations. With R p = 1.703 0.070 R J, HAT-P-64b is a highly inflated hot Jupiter around a star nearing the end of its main-sequence lifetime, and is among the largest known planets. Five of the seven systems have long-cadence observations by TESS which are included in the analysis. Of particular note is HAT-P-59 (TOI-1826.01) which is within the northern continuous viewing zone of the TESS mission, and HAT-P-60, which is the TESS candidate TOI-1580.01. © 2021. The American Astronomical Society. All rights reserved..
5 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Kepler-15b: A hot jupiter enriched in heavy elements and the first kepler mission planet confirmed with the hobby-eberly telescope - Endl, Michael; Macqueen, Phillip J; Cochran, William D; Brugamyer, Erik; Buchhave, Lars A; Rowe, Jason F; Lucas, P W; Isaacson, Howard; Bryson, Steve; Howell, Steve B; Fortney, Jonathan J; Hansen, Terese; et al. (Astrophysical Journal Supplement Series, 2011)
We report the discovery of Kepler-15b (KOI-128), a new transiting exoplanet detected by NASA's Kepler mission. The transit signal with a period of 4.94days was detected in the quarter 1 (Q1) Kepler photometry. For the first time, we have used the High Resolution Spectrograph (HRS) at the Hobby-Eberly Telescope (HET) to determine the mass of a Kepler planet via precise radial velocity (RV) measurements. The 24 HET/HRS RVs and 6 additional measurements from the Fibre-fed chelle Spectrograph spectrograph at the Nordic Optical Telescope reveal a Doppler signal with the same period and phase as the transit ephemeris. We used one HET/HRS spectrum of Kepler-15 taken without the iodine cell to determine accurate stellar parameters. The host star is a metal-rich ([Fe/H]= 0.36 ± 0.07) G-type main-sequence star with Teff = 5515 ± 124 K. The semi-amplitude K of the RV orbit is 78.7+8.5 -9.5ms-1, which yields a planet mass of 0.66 ± 0.1 M Jup. The planet has a radius of 0.96 ± 0.06R Jup and a mean bulk density of 0.9 ± 0.2 gcm-3. The radius of Kepler-15b is smaller than the majority of transiting planets with similar mass and irradiation level. This suggests that the planet is more enriched in heavy elements than most other transiting giant planets. For Kepler-15b we estimate a heavy element mass of 30-40 M ⊕. © 2011. The American Astronomical Society. All rights reserved.
23 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/001-839-775-387-264 tex.type: [object Object]
Keywords: dept.phy; planetary systems; stars: individual (Kepler-15; KOI-128; KIC 11359879; 2MASS J19444814+4908244); techniques: image processing; techniques: photometric; techniques: radial Velocities; techniques: spectroscopic

The infrared light curve of SN 2011fe in m101 and the distance to m101 - Matheson, Thomas; Joyce, Richard R; Allen, Lori E; Saha, A; Silva, David R; Woodvasey, W M; Adams, Joshua J; Anderson, R E; Beck, Tracy L; Bentz, Misty C; Bershady, Matthew A; Binkert, W S; et al. (The Astrophysical Journal, 2012)
We present near-infrared light curves of supernova (SN) 2011fe in M101, including 34 epochs in H band starting 14days before maximum brightness in the B band. The light curve data were obtained with the WIYN High-Resolution Infrared Camera. When the data are calibrated using templates of other Type Ia SNe, we derive an apparent H-band magnitude at the epoch of B-band maximum of 10.85 ± 0.04. This implies a distance modulus for M101 that ranges from 28.86 to 29.17mag, depending on which absolute calibration for Type Ia SNe is used. © © 2012. The American Astronomical Society. All rights reserved..
61 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/106-877-142-339-654 tex.type: [object Object]
Keywords: dept.phy; galaxies: distances and redshifts; galaxies: individual (M101); supernovae: individual (SN 2011fe)

Kepler-20: a sun-like star with three sub-neptune exoplanets and two earth-size candidates - Gautier, Thomas N.; Charbonneau, David; Rowe, Jason F.; Marcy, Geoffrey W.; Isaacson, Howard; Torres, Guillermo; Fressin, Francois; Rogers, Leslie A.; Désert, Jean-Michel; Buchhave, Lars A.; Latham, David W.; Quinn, Samuel N.; et al. (The Astrophysical Journal, 2012)
We present the discovery of the Kepler-20 planetary system, which we initially identified through the detection of five distinct periodic transit signals in the Kepler light curve of the host star 2MASS J19104752+4220194. From high-resolution spectroscopy of the star, we find a stellar effective temperature T eff = 5455 100 K, a metallicity of [Fe/H] = 0.01 0.04, and a surface gravity of log g = 4.4 0.1. We combine these estimates with an estimate of the stellar density derived from the transit light curves to deduce a stellar mass of M = 0.912 0.034 M and a stellar radius of R = 0.944 +0.060 -0.095 R. For three of the transit signals, we demonstrate that our results strongly disfavor the possibility that these result from astrophysical false positives. We accomplish this by first identifying the subset of stellar blends that reproduce the precise shape of the light curve and then using the constraints on the presence of additional stars from high angular resolution imaging, photometric colors, and the absence of a secondary component in our spectroscopic observations. We conclude that the planetary scenario is more likely than that of an astrophysical false positive by a factor of 2 × 105 (Kepler-20b), 1 × 105 (Kepler-20c), and 1.1 × 103 (Kepler-20d), sufficient to validate these objects as planetary companions. For Kepler-20c and Kepler-20d, the blend scenario is independently disfavored by the achromaticity of the transit: from Spitzer data gathered at 4.5 μm, we infer a ratio of the planetary to stellar radii of 0.075 0.015 (Kepler-20c) and 0.065 0.011 (Kepler-20d), consistent with each of the depths measured in the Kepler optical bandpass. We determine the orbital periods and physical radii of the three confirmed planets to be 3.70days and 1.91+0.12 -0.21 R ⊕ for Kepler-20b, 10.85days and 3.07+0.20 -0.31 R ⊕ for Kepler-20c, and 77.61days and 2.75+0.17 -0.30 R ⊕ for Kepler-20d. From multi-epoch radial velocities, we determine the masses of Kepler-20b and Kepler-20c to be 8.7 2.2 M ⊕ and 16.1 3.5 M ⊕, respectively, and we place an upper limit on the mass of Kepler-20d of 20.1 M ⊕ (2σ). © 2012 The American Astronomical Society. All rights reserved.
99 citations (Crossref) [2023-10-31] Citation Key Alias: pop00006 tex.type: [object Object]
Keywords: dept.phy; eclipses; planetary systems

A sub-Mercury-sized exoplanet. - Barclay, Thomas; Rowe, Jason; Lissauer, Jack; Huber, Daniel; Fressin, Francois; Howell, Steve; Bryson, Stephen; Chaplin, William; Desert, Jean-Michel; Lopez, Eric; Marcy, Geoffrey; Mullally, Fergal; et al. (Nature, 2013)
Since the discovery of the first exoplanets, it has been known that other planetary systems can look quite unlike our own. Until fairly recently, we have been able to probe only the upper range of the planet size distribution, and, since last year, to detect planets that are the size of Earth or somewhat smaller. Hitherto, no planets have been found that are smaller than those we see in the Solar System. Here we report a planet significantly smaller than Mercury. This tiny planet is the innermost of three that orbit the Sun-like host star, which we have designated Kepler-37. Owing to its extremely small size, similar to that of the Moon, and highly irradiated surface, the planet, Kepler-37b, is probably rocky with no atmosphere or water, similar to Mercury. © 2013 Macmillan Publishers Limited. All rights reserved.
161 citations (Crossref) [2023-10-31] Place: (C) 2013 Nature Publishing Group
Keywords: Earth; article; astronomy; atmosphere; dept.phy; irradiance; irradiation; moon; orbit determination; planetary surface; priority journal; size structure; solar system; sun; water

TOI-150b and TOI-163b: two transiting hot Jupiters, one eccentric and one inflated, revealed by TESS near and at the edge of the JWST CVZ - Kossakowski, Diana; Espinoza, Néstor; Brahm, Rafael; Jordán, Andrés; Henning, Thomas; Rojas, Felipe; Kürster, Martin; Sarkis, Paula; Schlecker, Martin; Pozuelos, F. J.; Barkaoui, Khalid; Jehin, Emmanuel; et al. (Monthly Notices of the Royal Astronomical Society, 2019)
We present the discovery of TYC9191-519-1b (TOI-150b, TIC 271893367) and HD271181b (TOI-163b, TIC 179317684), two hot Jupiters initially detected using 30-min cadence Transiting Exoplanet Survey Satellite (TESS) photometry from Sector 1 and thoroughly characterized through follow-up photometry (CHAT, Hazelwood, LCO/CTIO, El Sauce, TRAPPIST-S), high-resolution spectroscopy (FEROS, CORALIE), and speckle imaging (Gemini/DSSI), confirming the planetary nature of the two signals. A simultaneous joint fit of photometry and radial velocity using a new fitting package JULIET reveals that TOI-150b is a 1.254 ± 0.016 RJ, massive (2.61+−001912 MJ) hot Jupiter in a 5.857-d orbit, while TOI-163b is an inflated (RP = 1.478+−00022029 RJ, MP = 1.219 ± 0.11 MJ) hot Jupiter on a P = 4.231-d orbit; both planets orbit F-type stars. A particularly interesting result is that TOI-150b shows an eccentric orbit (e = 0.262+−00045037), which is quite uncommon among hot Jupiters. We estimate that this is consistent, however, with the circularization time-scale, which is slightly larger than the age of the system. These two hot Jupiters are both prime candidates for further characterization – in particular, both are excellent candidates for determining spin-orbit alignments via the Rossiter–McLaughlin (RM) effect and for characterizing atmospheric thermal structures using secondary eclipse observations considering they are both located closely to the James Webb Space Telescope (JWST) Continuous Viewing Zone (CVZ). © 2018 The Author(s) Published by Oxford University Press on behalf of the Royal Astronomical Society.
15 citations (Crossref) [2023-10-31] Citation Key Alias: pop00004 tex.type: [object Object]
Keywords: Planets and satellites: detection; Stars: individual: HD271181; Stars: individual: TIC 179317684; Stars: individual: TIC 271893367; Stars: individual: TYC9191-519-1; Techniques: photometric; dept.phy; peer-reviewed

197 candidates and 104 validated planets in k2's first five fields - Crossfield, Ian J M; Ciardi, David R; Petigura, Erik A; Sinukoff, Evan; Schlieder, Joshua E; Schlieder, Joshua E; Howard, Andrew W; Beichman, Charles A; Isaacson, Howard; Dressing, Courtney D; Christiansen, Jessie L; Fulton, Benjamin J; et al. (Astrophysical Journal Supplement Series, 2016)
We present 197 planet candidates discovered using data from the first year of the NASA K2 mission (Campaigns 0-4), along with the results of an intensive program of photometric analyses, stellar spectroscopy, high-resolution imaging, and statistical validation. We distill these candidates into sets of 104 validated planets (57 in multi-planet systems), false positives, and 63 remaining candidates. Our validated systems span a range of properties, with median values of RP= 2.3 R⊕, P = 8.6 days, Teff = 5300 K, and Kp = 12.7mag. Stellar spectroscopy provides precise stellar and planetary parameters for most of these systems. We show that K2 has increased by 30% the number of small planets known to orbit moderately bright stars (1-4 R R⊕, Kp = 9-13 mag). Of particular interest are planets smaller than 2 R⊕, orbiting stars brighter than Kp = 11.5 mag, 5 receiving Earth-like irradiation levels, and several multi-planet systems - including 4 planets orbiting the M dwarf K2-72 near mean-motion resonances. By quantifying the likelihood that each candidate is a planet we demonstrate that our candidate sample has an overall false positive rate of 15%-30%, with rates substantially lower for small candidates (<2R⊕) and larger for candidates with radii >8 R⊕ and/or with P<3 days. Extrapolation of the current planetary yield suggests that K2 will discover between 500 and 1000 planets in its planned four-year mission, assuming sufficient follow-up resources are available. Efficient observing and analysis, together with an organized and coherent follow-up strategy, are essential for maximizing the efficacy of planet-validation efforts for K2, TESS, and future large-scale surveys. © 2016. The American Astronomical Society. All rights reserved.
150 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/016-053-995-602-624 tex.type: [object Object]
Keywords: catalogs; dept.phy; planets and satellites: fundamental parameters; planets and satellites: general; techniques: high angular resolution; techniques: photometric; techniques: spectroscopic

Kepler-14b: A Massive Hot Jupiter Transiting an F Star in a Close Visual Binary - Buchhave, Lars A; Latham, David W; Carter, Joshua A; Desert, J M; Torres, Guillermo; Adams, Elisabeth R; Bryson, Stephen T; Charbonneau, David; Ciardi, David R; Kulesa, Craig; Dupree, Andrea K; Fischer, Debra A; et al. (Astrophysical Journal Supplement Series, 2011)
We present the discovery of a hot Jupiter transiting an F star in a close visual (03 sky projected angular separation) binary system. The dilution of the host star's light by the nearly equalmagnitude stellar companion (∼0.5mag fainter) significantly affects the derived planetary parameters, and if left uncorrected, leads to an underestimate of the radius and mass of the planet by 10% and 60%, respectively. Other published exoplanets, which have not been observed with high-resolution imaging, could similarly have unresolved stellar companions and thus have incorrectly derived planetary parameters. Kepler-14b (KOI-98) has a period of P = 6.790 days and, correcting for the dilution, has a mass of Mp = 8.40+0.35 -0.34 M J and a radius of Rp = 1.136+0.073-0.054 R J, yielding a mean density of ρp = 7.1 ± 1.1 g cm-3. © 2011. The American Astronomical Society. All rights reserved.
52 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/073-747-569-084-362 tex.type: [object Object]
Keywords: dept.phy; planetary systems; stars: individual (Kepler-14b; KIC 10264660; 2MASS J19105011+4719589); techniques: photometric; techniques: spectroscopic

Transit timing observations from kepler: III. confirmation of 4 multiple planet systems by a fourier-domain study of anti-correlated transit timing variations - Steffen, Jason H.; Fabrycky, Daniel C.; Ford, Eric B.; Carter, Joshua A.; Désert, Jean-Michel; Fressin, Francois; Holman, Matthew J.; Lissauer, Jack J.; Moorhead, Althea V.; Rowe, Jason F.; Ragozzine, Darin; Welsh, William F.; et al. (Monthly Notices of the Royal Astronomical Society, 2012)
We present a method to confirm the planetary nature of objects in systems with multiple transiting exoplanet candidates. This method involves a Fourier-domain analysis of the deviations in the transit times from a constant period that result from dynamical interactions within the system. The combination of observed anticorrelations in the transit times and mass constraints from dynamical stability allow us to claim the discovery of four planetary systems, Kepler-25, Kepler-26, Kepler-27 and Kepler-28, containing eight planets and one additional planet candidate. © 2012 Fermi Research Alliance LLC, Contractor for the U.S. Dept of Energy Monthly Notices of the Royal Astronomical Society © 2012 RAS.
121 citations (Crossref) [2023-10-31] Citation Key Alias: pop00008 tex.type: [object Object]
Keywords: Celestial mechanics; Methods: data analysis; Stars: individual: KIC 4349452; Stars: individual: KIC 5792202; Stars: individual: KIC 6949607; Stars: individual: KIC 9757613; dept.phy; peer-reviewed

Transit timing observations from kepler. II. confirmation of two multiplanet systems via a non-parametric correlation analysis - Ford, Eric B.; Fabrycky, Daniel C.; Steffen, Jason H.; Carter, Joshua A.; Fressin, Francois; Holman, Matthew J.; Lissauer, Jack J.; Moorhead, Althea V.; Morehead, Robert C.; Ragozzine, Darin; Rowe, Jason F.; Welsh, William F.; et al. (The Astrophysical Journal, 2012)
We present a new method for confirming transiting planets based on the combination of transit timing variations (TTVs) and dynamical stability. Correlated TTVs provide evidence that the pair of bodies is in the same physical system. Orbital stability provides upper limits for the masses of the transiting companions that are in the planetary regime. This paper describes a non-parametric technique for quantifying the statistical significance of TTVs based on the correlation of two TTV data sets. We apply this method to an analysis of the TTVs of two stars with multiple transiting planet candidates identified by Kepler. We confirm four transiting planets in two multiple-planet systems based on their TTVs and the constraints imposed by dynamical stability. An additional three candidates in these same systems are not confirmed as planets, but are likely to be validated as real planets once further observations and analyses are possible. If all were confirmed, these systems would be near 4:6:9 and 2:4:6:9 period commensurabilities. Our results demonstrate that TTVs provide a powerful tool for confirming transiting planets, including low-mass planets and planets around faint stars for which Doppler follow-up is not practical with existing facilities. Continued Kepler observations will dramatically improve the constraints on the planet masses and orbits and provide sensitivity for detecting additional non-transiting planets. If Kepler observations were extended to eight years, then a similar analysis could likely confirm systems with multiple closely spaced, small transiting planets in or near the habitable zone of solar-type stars. © 2012. The American Astronomical Society. All rights reserved.
73 citations (Crossref) [2023-10-31] Citation Key Alias: pop00013 tex.type: [object Object]
Keywords: dept.phy; planetary systems; planets and satellites: detection; planets and satellites: dynamical evolution and stability; stars: individual (KIC 3231341; 11512246; KOI 168; 1102; Kepler-23; Kepler-24); techniques: miscellaneous

Kepler-18b, c, and d: a system of three planets confirmed by transit timing variations, light curve validation, warm-spitzer photometry, and radial velocity measurements* - Cochran, William D.; Fabrycky, Daniel C.; Torres, Guillermo; Fressin, Francois; Désert, Jean-Michel; Ragozzine, Darin; Sasselov, Dimitar; Fortney, Jonathan J.; Rowe, Jason F.; Brugamyer, Erik; Bryson, Stephen T.; Carter, Joshua A.; et al. (Astrophysical Journal Supplement Series, 2011)
We report the detection of three transiting planets around a Sun-like star, which we designate Kepler-18. The transit signals were detected in photometric data from the Kepler satellite, and were confirmed to arise from planets using a combination of large transit-timing variations (TTVs), radial velocity variations, Warm-Spitzer observations, and statistical analysis of false-positive probabilities. The Kepler-18 star has a mass of 0.97 M ⊙, a radius of 1.1 R ⊙, an effective temperature of 5345K, and an iron abundance of [Fe/H] = +0.19. The planets have orbital periods of approximately 3.5, 7.6, and 14.9 days. The innermost planet "b" is a "super-Earth" with a mass of 6.9 ± 3.4 M ⊕, a radius of 2.00 ± 0.10 R ⊕, and a mean density of 4.9 ± 2.4gcm3. The two outer planets "c" and "d" are both low-density Neptune-mass planets. Kepler-18c has a mass of 17.3 ± 1.9 M ⊕, a radius of 5.49 ± 0.26 R ⊕, and a mean density of 0.59 0.07gcm 3, while Kepler-18d has a mass of 16.4 ± 1.4 M ⊕, a radius of 6.98 ± 0.33 R ⊕ and a mean density of 0.27 ± 0.03gcm3. Kepler-18c and Kepler-18d have orbital periods near a 2:1 mean-motion resonance, leading to large and readily detected TTVs. © 2011. The American Astronomical Society. All rights reserved.
144 citations (Crossref) [2023-10-31] Citation Key Alias: pop00006 tex.type: [object Object]
Keywords: dept.phy; planetary systems; stars: individual (Kepler-18; KIC 8644288; 2MASS J19521906+4444467); techniques: photometric; techniques: spectroscopic

Kepler Planet-Detection Mission: Introduction and First Results. - Borucki, William; Koch, David; Basri, Gibor; Batalha, Natalie; Brown, Timothy; Caldwell, Douglas; Caldwell, John; Christensen-Dalsgaard, Jorgen; Cochran, William; DeVore, Edna; Dunham, Edward; Dupree, Andrea; et al. (Science, 2010)
The Kepler mission was designed to determine the frequency of Earth-sized planets in and near the habitable zone of Sun-like stars. The habitable zone is the region where planetary temperatures are suitable for water to exist on a planet's surface. During the first 6 weeks of observations, Kepler monitored 156,000 stars, and five new exoplanets with sizes between 0.37 and 1.6 Jupiter radii and orbital periods from 3.2 to 4.9 days were discovered. The density of the Neptune-sized Kepler-4b is similar to that of Neptune and GJ 436b, even though the irradiation level is 800,000 times higher. Kepler-7b is one of the lowest-density planets (∼0.17 gram per cubic centimeter) yet detected. Kepler-5b, -6b, and -8b confirm the existence of planets with densities lower than those predicted for gas giant planets.
2612 citations (Crossref) [2023-10-31] Place: Copyright (C) 2010 by the American Association for the Advancement of Science
Keywords: Jupiter; article; astronomy; astrophysics; density; dept.phy; gas; irradiation; planetary atmosphere; planetary surface; priority journal; spacecraft; sun; temperature; water

Characteristics of kepler planetary candidates based on the first data set - Borucki, William J.; Koch, David G.; Basri, Gibor; Batalha, Natalie M.; Boss, Alan P.; Brown, Timothy M.; Caldwell, Douglas A.; Christensen-Dalsgaard, Jørgen; Cochran, William D.; DeVore, Edna; Dunham, Edward W.; Dupree, Andrea K.; et al. (The Astrophysical Journal, 2011)
In the spring of 2009, the Kepler Mission commenced high-precision photometry on nearly 156,000 stars to determine the frequency and characteristics of small exoplanets, conduct a guest observer program, and obtain asteroseismic data on a wide variety of stars. On 2010 June 15, the Kepler Mission released most of the data from the first quarter of observations. At the time of this data release, 705 stars from this first data set have exoplanet candidates with sizes from as small as that of Earth to larger than that of Jupiter. Here we give the identity and characteristics of 305 released stars with planetary candidates. Data for the remaining 400 stars with planetary candidates will be released in 2011 February. More than half the candidates on the released list have radii less than half that of Jupiter. Five candidates are present in and near the habitable zone; two near super-Earth size, and three bracketing the size of Jupiter. The released stars also include five possible multi-planet systems. One of these has two Neptune-size (2.3 and 2.5 Earth radius) candidates with near-resonant periods. © 2011. The American Astronomical Society.
282 citations (Crossref) [2023-10-31] Citation Key Alias: pop00003 tex.type: [object Object]
Keywords: Planets and satellites: detection; Surveys; dept.phy

KEPLER-21b: A 1.6 REarth planet transiting the bright oscillating F subgiant star HD179070 - Howell, Steve B.; Rowe, Jason F.; Bryson, Stephen T.; Quinn, Samuel N.; Marcy, Geoffrey W.; Isaacson, Howard; Ciardi, David R.; Chaplin, William J.; Metcalfe, Travis S.; Monteiro, Mário J. P. F. G.; Appourchaux, Thierry; Basu, Sarbani; et al. (The Astrophysical Journal, 2012)
We present Kepler observations of the bright (V = 8.3), oscillating star HD179070. The observations show transit-like events which reveal that the star is orbited every 2.8days by a small, 1.6 R Earth object. Seismic studies of HD179070 using short cadence Kepler observations show that HD179070 has a frequency-power spectrum consistent with solar-like oscillations that are acoustic p-modes. Asteroseismic analysis provides robust values for the mass and radius of HD179070, 1.34 ± 0.06 M ⊙ and 1.86 ± 0.04 R ⊙, respectively, as well as yielding an age of 2.84 ± 0.34Gyr for this F5 subgiant. Together with ground-based follow-up observations, analysis of the Kepler light curves and image data, and blend scenario models, we conservatively show at the >99.7% confidence level (3σ) that the transit event is caused by a 1.64 0.04 R Earth exoplanet in a 2.785755 ± 0.000032day orbit. The exoplanet is only 0.04 AU away from the star and our spectroscopic observations provide an upper limit to its mass of ∼10 M Earth (2σ). HD179070 is the brightest exoplanet host star yet discovered by Kepler. © 2012. The American Astronomical Society. All rights reserved.
101 citations (Crossref) [2023-10-31] Citation Key Alias: pop00009 tex.type: [object Object]
Keywords: dept.phy; planetary systems; stars: activity; stars: individual (HD 179070: KIC 3632418); stars: interiors; stars: late-type; stars: magnetic field; stars: oscillations (including pulsations); techniques: photometric

Characteristics of planetary candidates observed by Kepler II : Analysis of the first four months of data - Borucki, William J.; Koch, David G.; Basri, Gibor; Batalha, Natalie M.; Brown, Timothy M.; Bryson, Stephen T.; Caldwell, Douglas A.; Christensen-Dalsgaard, Jørgen; Cochran, William D.; DeVore, Edna; Dunham, Edward W.; Gautier, Thomas N.; et al. (The Astrophysical Journal, 2011)
On 2011 February 1 the Kepler mission released data for 156,453 stars observed from the beginning of the science observations on 2009 May 2 through September 16. There are 1235 planetary candidates with transit-like signatures detected in this period. These are associated with 997 host stars. Distributions of the characteristics of the planetary candidates are separated into five class sizes: 68 candidates of approximately Earth-size (Rp < 1.25 R⊕), 288 super-Earth-size (1.25 R⊕ ≤ R p < 2 R⊕), 662 Neptune-size (2 R ⊕ ≤ Rp < 6 R⊕), 165 Jupiter-size (6 R⊕ ≤ Rp < 15 R ⊕), and 19 up to twice the size of Jupiter (15 R ⊕ ≤ Rp < 22 R⊕). In the temperature range appropriate for the habitable zone, 54 candidates are found with sizes ranging from Earth-size to larger than that of Jupiter. Six are less than twice the size of the Earth. Over 74% of the planetary candidates are smaller than Neptune. The observed number versus size distribution of planetary candidates increases to a peak at two to three times the Earth-size and then declines inversely proportional to the area of the candidate. Our current best estimates of the intrinsic frequencies of planetary candidates, after correcting for geometric and sensitivity biases, are 5% for Earth-size candidates, 8% for super-Earth-size candidates, 18% for Neptune-size candidates, 2% for Jupiter-size candidates, and 0.1% for very large candidates; a total of 0.34 candidates per star. Multi-candidate, transiting systems are frequent; 17% of the host stars have multi-candidate systems, and 34% of all the candidates are part of multi-candidate systems. © 2011. The American Astronomical Society. All rights reserved.
799 citations (Crossref) [2023-10-31] Citation Key Alias: pop00002 tex.type: [object Object]
Keywords: dept.phy; planetary systems; planets and satellites: detection; stars: statistics; surveys

Near-resonance in a System of Sub-Neptunes from TESS - Quinn, Samuel N.; Becker, Juliette C.; Rodriguez, Joseph E.; Hadden, Sam; Huang, Chelsea X.; Morton, Timothy D.; Adams, Fred C.; Armstrong, David; Eastman, Jason D.; Horner, Jonathan; Kane, Stephen R.; Lissauer, Jack J.; et al. (The Astronomical Journal, 2019)
We report the Transiting Exoplanet Survey Satellite detection of a multi-planet system orbiting the V = 10.9 K0 dwarf TOI-125. We find evidence for up to five planets, with varying confidence. Three transit signals with high signal-to-noise ratio correspond to sub-Neptune-sized planets (2.76, 2.79, and 2.94 R⊕), and we statistically validate the planetary nature of the two inner planets (Pb = 4.65 days, Pc = 9.15 days). With only two transits observed, we report the outer object (P.03 = 19.98 days) as a planet candidate with high signal-to-noise ratio. We also detect a candidate transiting super-Earth (1.4 R⊕) with an orbital period of only 12.7 hr and a candidate Neptune-sized planet (4.2 R⊕) with a period of 13.28 days, both at low signal-to-noise ratio. This system is amenable to mass determination via radial velocities and transit-timing variations, and provides an opportunity to study planets of similar size while controlling for age and environment. The ratio of orbital periods between TOI-125 b and c (Pc/Pb = 1.97) is slightly lower than an exact 2:1 commensurability and is atypical of multiple planet systems from Kepler, which show a preference for period ratios just wide of first-order period ratios. A dynamical analysis refines the allowed parameter space through stability arguments and suggests that despite the nearly commensurate periods, the system is unlikely to be in resonance.
Keywords: dept.phy; peer-reviewed

Kepler-22b: A 2.4 Earth-radius Planet in the Habitable Zone of a Sun-like Star - Borucki, William J.; Koch, David G.; Batalha, Natalie M.; Bryson, Stephen T.; Rowe, Jason F.; Fressin, Francois; Torres, Guillermo; Caldwell, Douglas A.; Christensen-Dalsgaard, Jørgen; Cochran, William D.; DeVore, Edna; Gautier, Thomas N.; et al. (The Astrophysical Journal, 2012)
A search of the time-series photometry from NASA's Kepler spacecraft reveals a transiting planet candidate orbiting the 11th magnitude G5 dwarf KIC 10593626 with a period of 290 days. The characteristics of the host star are well constrained by high-resolution spectroscopy combined with an asteroseismic analysis of the Kepler photometry, leading to an estimated mass and radius of 0.970 0.060 M and 0.979 0.020 R. The depth of 492 10 ppm for the three observed transits yields a radius of 2.38 0.13 Re for the planet. The system passes a battery of tests for false positives, including reconnaissance spectroscopy, high-resolution imaging, and centroid motion. A full BLENDER analysis provides further validation of the planet interpretation by showing that contamination of the target by an eclipsing system would rarely mimic the observed shape of the transits. The final validation of the planet is provided by 16 radial velocities (RVs) obtained with the High Resolution Echelle Spectrometer on Keck I over a one-year span. Although the velocities do not lead to a reliable orbit and mass determination, they are able to constrain the mass to a 3σ upper limit of 124 M ⊕, safely in the regime of planetary masses, thus earning the designation Kepler-22b. The radiative equilibrium temperature is 262 K for a planet in Kepler-22b's orbit. Although there is no evidence that Kepler-22b is a rocky planet, it is the first confirmed planet with a measured radius to orbit in the habitable zone of any star other than the Sun. © 2012. The American Astronomical Society. All rights reserved.
186 citations (Crossref) [2023-10-31] Citation Key Alias: pop00003 tex.type: [object Object]
Keywords: dept.phy; planetary systems; stars: fundamental parameters; stars: individual (Kepler-22; KIC 10593626)

The L 98-59 system: Three transiting, terrestrial-size planets orbiting a nearby M dwarf - Kostov, Veselin B.; Schlieder, Joshua E.; Barclay, Thomas; Quintana, Elisa V.; Colón, Knicole D.; Brande, Jonathan; Collins, Karen A.; Feinstein, Adina D.; Hadden, Samuel; Kane, Stephen R.; Kreidberg, Laura; Kruse, Ethan; et al. (The Astronomical Journal, 2019)
We report the Transiting Exoplanet Survey Satellite (TESS) discovery of three terrestrial-size planets transiting L 98-59 (TOI-175, TIC 307210830)—a bright M dwarf at a distance of 10.6 pc. Using the Gaia-measured distance and broadband photometry, we find that the host star is an M3 dwarf. Combined with the TESS transits from three sectors, the corresponding stellar parameters yield planet radii ranging from 0.8 R ⊕ to 1.6 R ⊕. All three planets have short orbital periods, ranging from 2.25 to 7.45 days with the outer pair just wide of a 2:1 period resonance. Diagnostic tests produced by the TESS Data Validation Report and the vetting package DAVE rule out common false-positive sources. These analyses, along with dedicated follow-up and the multiplicity of the system, lend confidence that the observed signals are caused by planets transiting L 98-59 and are not associated with other sources in the field. The L 98-59 system is interesting for a number of reasons: the host star is bright (V = 11.7 mag, K = 7.1 mag) and the planets are prime targets for further follow-up observations including precision radial-velocity mass measurements and future transit spectroscopy with the James Webb Space Telescope; the near-resonant configuration makes the system a laboratory to study planetary system dynamical evolution; and three planets of relatively similar size in the same system present an opportunity to study terrestrial planets where other variables (age, metallicity, etc.) can be held constant. L 98-59 will be observed in four more TESS sectors, which will provide a wealth of information on the three currently known planets and have the potential to reveal additional planets in the system.
80 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/007-363-095-757-409, pop00014 tex.type: [object Object]
Keywords: dept.phy; peer-reviewed; planets and satellites: detection; stars: individual (TIC 307210830; TOI-175); techniques: photometric